Adhesive composition and laminate

JP7651892B2Active Publication Date: 2025-03-27NISSAN CHEM CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021041154
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-15
Publication Date
2025-03-27
Estimated Expiration
2041-03-15

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、半導体基板と支持基板とを好適に仮接着可能である接着層を与え、且つ、保存安定性に優れる接着剤組成物を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007651892000026
    Figure 0007651892000026
  • Figure 0007651892000027
    Figure 0007651892000027
  • Figure 0007651892000028
    Figure 0007651892000028
Patent Text Reader

Abstract

To provide an adhesive composition which gives an adhesive layer capable of suitably temporarily bonding a semiconductor substrate and a support substrate together and is excellent in storage stability.SOLUTION: The adhesive composition to be used to form an adhesive layer for temporary bonding for processing a semiconductor substrate contains a thermosetting adhesive component and thermally expandable particles. The thermosetting adhesive component contains a polyorganosiloxane. The thermally expandable particles are contained in an amount of 3.5 mass% or less based on the thermosetting adhesive component.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive composition and a laminate. [Background technology]

[0002] Conventionally, semiconductor wafers have been integrated in a two-dimensional plane, but for the purpose of further integration, there is a demand for semiconductor integration technology that integrates (stacks) the plane in a three-dimensional direction. This three-dimensional stacking is a technology that integrates multiple layers while connecting them with through silicon vias (TSVs). When integrating multiple layers, each wafer to be integrated is thinned by polishing the side opposite the circuit surface (i.e., the back side), and the thinned semiconductor wafers are stacked. An unthinned semiconductor wafer (also referred to herein simply as a wafer) is attached to a support for polishing in a polishing apparatus. The adhesive at this time must be easily peeled off after polishing, so it is called temporary adhesive. This temporary adhesive must be easily removed from the support, and if a large force is applied to remove it, the thinned semiconductor wafer may be cut or deformed, so it is easily removed to prevent such things from happening. However, it is undesirable for the adhesive to come off or shift due to the polishing stress when polishing the back surface of the semiconductor wafer. Therefore, the performance required for the temporary adhesive is to withstand the stress during polishing and to be easily removed after polishing. For example, the material is required to have high stress (strong adhesive strength) in the planar direction during polishing, and low stress (weak adhesive strength) in the vertical direction during removal.

[0003] Under the above circumstances, the inventors have reported adhesive compositions that contain a component that cures via a hydrosilylation reaction as well as a component such as polydimethylsiloxane as an adhesive composition that can achieve such temporary adhesion (see, for example, Patent Documents 1 and 2).

[0004] Meanwhile, Patent Document 3 proposes a silicone composition for temporary adhesion that contains a thermally expandable powder in order to provide an adhesive that can be separated in a relatively simple manner and / or without leaving any residue. However, the present inventors confirmed that when thermally expandable particles are contained in an adhesive composition in the amount described in the examples of Patent Document 3, an adhesive composition with good storage stability cannot be obtained. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2017 / 221772 [Patent Document 2] International Publication No. 2018 / 216732 [Patent Document 3] Special publication 2020-529488 Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention has been made in consideration of the above circumstances, and has an object to provide an adhesive composition that provides an adhesive layer that can suitably temporarily bond a semiconductor substrate and a supporting substrate, and that has excellent storage stability. [Means for solving the problem]

[0007] Means for Solving the Problems The present inventors have conducted intensive research to solve the above-mentioned problems and have completed the present invention having the following gist.

[0008] That is, the present invention includes the following. [1] An adhesive composition used to form an adhesive layer for temporary bonding in order to process a semiconductor substrate, A thermosetting adhesive component and a thermally expandable particle are included, The thermosetting adhesive component contains a polyorganosiloxane, The adhesive composition contains the thermally expandable particles in an amount of 3.5 mass % or less based on the thermosetting adhesive component. [2] The adhesive composition according to [1], wherein the thermosetting adhesive component is a component that cures by a hydrosilylation reaction. [3] A laminate including an adhesive layer interposed between a semiconductor substrate and a support substrate and in contact with the semiconductor substrate, The adhesive layer is a layer formed from the adhesive composition according to [1] or [2]. [4] A method for improving the storage stability of an adhesive composition used to form an adhesive layer for temporary bonding in processing a semiconductor substrate, the adhesive composition comprising a thermosetting adhesive component containing polyorganosiloxane and thermally expandable particles, comprising: A method for improving the storage stability of an adhesive composition, comprising: setting the content of the thermally expandable particles to 3.5 mass % or less based on the thermosetting adhesive component. Effect of the Invention

[0009] According to the present invention, it is possible to provide an adhesive composition which provides an adhesive layer capable of suitably temporarily bonding a semiconductor substrate and a supporting substrate and has excellent storage stability. [Brief description of the drawings]

[0010] [Figure 1A] FIG. 2 is a schematic cross-sectional view of an example of a laminate. [Figure 1B] FIG. 4 is a schematic cross-sectional view of another example of a laminate. [Figure 2A] FIG. 1 is a diagram (part 1) for explaining one embodiment of manufacturing a laminate and a thinned wafer. [Figure 2B] FIG. 2 is a diagram (part 2) for explaining one embodiment of manufacturing a laminate and a thinned wafer. [Figure 2C] FIG. 3 is a diagram (part 3) for explaining one embodiment of manufacturing a laminate and a thinned wafer. [Figure 2D] FIG. 4 is a diagram (part 4) for explaining one embodiment of manufacturing a laminate and a thinned wafer. [Figure 2E] FIG. 5 is a diagram (part 5) for explaining one embodiment of manufacturing a laminate and a thinned wafer. [Figure 2F] FIG. 6 is a diagram for explaining one embodiment of manufacturing a laminate and a thinned wafer. [Figure 3A] FIG. 7 is a diagram for explaining one embodiment of manufacturing a laminate and a thinned wafer. [Figure 3B] FIG. 8 is a diagram for explaining one embodiment of manufacturing a laminate and a thinned wafer. [Figure 3C] FIG. 9 is a diagram for explaining one embodiment of manufacturing a laminate and a thinned wafer. [Figure 3D] FIG. 10 is a diagram for explaining one embodiment of manufacturing a laminate and a thinned wafer. [Figure 3E] FIG. 11 is an eleventh diagram for explaining one embodiment of manufacturing a laminate and a thinned wafer. [Figure 3F] FIG. 12 is a diagram for explaining one embodiment of manufacturing a laminate and a thinned wafer. [Figure 3G] FIG. 13 is a diagram for explaining one embodiment of manufacturing a laminate and a thinned wafer. [Figure 3H] FIG. 14 is a diagram (part 14) for explaining one embodiment of manufacturing a laminate and a thinned wafer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] (Adhesive Composition) The adhesive composition of the present invention is a composition used for forming an adhesive layer for temporary adhesion in order to process semiconductor substrates. The adhesive composition of the present invention comprises a thermosetting adhesive component and thermally expandable particles. The thermosetting adhesive component contains a polyorganosiloxane. The adhesive composition of the present invention contains thermally expandable particles in an amount of 3.5 mass % or less based on the thermosetting adhesive component. The adhesive composition of the present invention may contain other components such as a solvent in addition to the thermosetting adhesive component and the thermally expandable particles, for example, to adjust the viscosity of the adhesive composition. As shown in the examples below, the adhesive composition of the present invention is capable of forming an adhesive layer that is easily peelable, and exhibits good storage stability with no precipitation even when stored for a long period of time.

[0012] <Thermosetting adhesive component> The thermosetting adhesive component contains a polyorganosiloxane. By including the polyorganosiloxane, the resulting adhesive layer can have excellent heat resistance. From the viewpoint of achieving excellent heat resistance in the resulting adhesive layer with good reproducibility, in a preferred embodiment, the thermosetting adhesive component contains a component that cures via a hydrosilylation reaction. A preferred embodiment of the thermosetting adhesive component used in the present invention includes, for example, a curing component (A) that becomes an adhesive component. The thermosetting adhesive component used in the present invention may include a curing component (A) that becomes an adhesive component and a component (B) that does not cause a curing reaction. Here, an example of the component (B) that does not cause a curing reaction is polyorganosiloxane. In the present invention, "does not cause a curing reaction" does not mean that any curing reaction does not occur, but means that the curing reaction occurring in the curing component (A) does not occur. In another preferred embodiment, component (A) may be a component that cures by a hydrosilylation reaction, or may be a polyorganosiloxane component (A') that cures by a hydrosilylation reaction. In another preferred embodiment, the component (A) contains, for example, a polyorganosiloxane (a1) having an alkenyl group having 2 to 40 carbon atoms bonded to a silicon atom, as an example of the component (A'), a polyorganosiloxane (a2) having a Si-H group, and a platinum group metal catalyst (A2). Here, the alkenyl group having 2 to 40 carbon atoms may be substituted. Examples of the substituent include a halogen atom, a nitro group, a cyano group, an amino group, a hydroxyl group, a carboxyl group, an aryl group, and a heteroaryl group. In another preferred embodiment, the polyorganosiloxane component (A') that cures by a hydrosilylation reaction comprises siloxane units (Q units) represented by SiO2, R 1 R 2 R 3 SiO 1 / 2 Siloxane unit (M unit) represented by R 4 R 5 SiO 2 / 2 Siloxane units (D units) represented by the formula 6 SiO 3 / 2 and a platinum group metal catalyst (A2). The polysiloxane (A1) contains one or more units selected from the group consisting of siloxane units (T units) represented by the following formula: 1 'R 2 'R 3 'SiO 1 / 2 Siloxane unit (M' unit) represented by R 4 'R 5 'SiO 2 / 2 Siloxane units (D' units) represented by the formula 6 'SiO 3 / 2 and at least one unit selected from the group consisting of M' units, D' units and T' units; and a polyorganosiloxane (a1') containing one or more units selected from the group consisting of siloxane units (T' units) represented by the following formula: 1 "R 2 "R 3 "SiO 1 / 2 Siloxane unit (M” unit) represented by R 4 "R 5 "SiO 2 / 2 Siloxane units (D" units) represented by the formula 6 "SiO 3 / 2 and a polyorganosiloxane (a2') containing one or more units selected from the group consisting of siloxane units (T" units) represented by the following formula: Note that (a1') is an example of (a1), and (a2') is an example of (a2).

[0013] R 1 ~R 6 are groups or atoms bonded to silicon atoms, each independently representing an optionally substituted alkyl group, an optionally substituted alkenyl group, or a hydrogen atom. Examples of the substituent include a halogen atom, a nitro group, a cyano group, an amino group, a hydroxyl group, a carboxyl group, an aryl group, and a heteroaryl group.

[0014] R 1 '~R 6 Each of R ′ is a group bonded to a silicon atom, and each independently represents an optionally substituted alkyl group or an optionally substituted alkenyl group. 1 '~R 6 At least one of the groups ' is an alkenyl group which may be substituted. Examples of the substituent include a halogen atom, a nitro group, a cyano group, an amino group, a hydroxyl group, a carboxyl group, an aryl group, and a heteroaryl group.

[0015] R 1 ”~R 6 " are groups or atoms bonded to the silicon atom, each independently representing an optionally substituted alkyl group or a hydrogen atom, R 1 ”~R 6 At least one of " is a hydrogen atom. Examples of the substituent include a halogen atom, a nitro group, a cyano group, an amino group, a hydroxyl group, a carboxyl group, an aryl group, and a heteroaryl group.

[0016] The alkyl group may be linear, branched, or cyclic, but is preferably a linear or branched alkyl group. The number of carbon atoms is not particularly limited, but is usually 1 to 40, preferably 30 or less, more preferably 20 or less, and even more preferably 10 or less.

[0017] Specific examples of the optionally substituted straight-chain or branched-chain alkyl group include a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, an i-butyl group, an s-butyl group, a tertiary butyl group, an n-pentyl group, a 1-methyl-n-butyl group, a 2-methyl-n-butyl group, a 3-methyl-n-butyl group, a 1,1-dimethyl-n-propyl group, a 1,2-dimethyl-n-propyl group, a 2,2-dimethyl-n-propyl group, a 1-ethyl-n-propyl group, an n-hexyl group, a 1-methyl-n-pentyl group, a 2-methyl-n-pentyl group, a 3-methyl-n-pentyl group, a 4-methyl-n-pentyl group, a 5-methyl-n-pentyl group, a 6-methyl-n-pentyl group, a 7-methyl-n-pentyl group, a 8-methyl-n-pentyl group, a 9-methyl-n-pentyl group, a 10-methyl-n-pentyl group, a 11-methyl-n-pentyl group, a 12-methyl-n-pentyl group, a 13-methyl-n-pentyl group, a 14-methyl-n-pentyl group, a 15-methyl-n-pentyl group, a 16-methyl-n-pentyl group, a 17-methyl-n-pentyl group, a 18-methyl-n-pentyl group, a 21-methyl-n-pentyl group, a 22-methyl-n-pentyl group, a 23-methyl-n-pentyl group, a 24-methyl-n-pentyl group, a 25-methyl-n-pentyl group, a 26-methyl-n-pentyl group, a 27-methyl-n-pentyl group, a 28-methyl-n-pentyl group, a 29-methyl-n-pentyl group, a 3 Examples of the alkyl group include, but are not limited to, a methyl group, a 1,1-dimethyl-n-butyl group, a 1,2-dimethyl-n-butyl group, a 1,3-dimethyl-n-butyl group, a 2,2-dimethyl-n-butyl group, a 2,3-dimethyl-n-butyl group, a 3,3-dimethyl-n-butyl group, a 1-ethyl-n-butyl group, a 2-ethyl-n-butyl group, a 1,1,2-trimethyl-n-propyl group, a 1,2,2-trimethyl-n-propyl group, a 1-ethyl-1-methyl-n-propyl group, and a 1-ethyl-2-methyl-n-propyl group, and the number of carbon atoms is usually 1 to 14, preferably 1 to 10, and more preferably 1 to 6. Among these, a methyl group is particularly preferable.

[0018] Specific examples of the optionally substituted cyclic alkyl group include a cyclopropyl group, a cyclobutyl group, a 1-methyl-cyclopropyl group, a 2-methyl-cyclopropyl group, a cyclopentyl group, a 1-methyl-cyclobutyl group, a 2-methyl-cyclobutyl group, a 3-methyl-cyclobutyl group, a 1,2-dimethyl-cyclopropyl group, a 2,3-dimethyl-cyclopropyl group, a 1-ethyl-cyclopropyl group, a 2-ethyl-cyclopropyl group, a cyclohexyl group, a 1-methyl-cyclopentyl group, a 2-methyl-cyclopentyl group, a 3-methyl-cyclopentyl group, a 1-ethyl-cyclobutyl group, a 2-ethyl-cyclobutyl group, a 3-ethyl-cyclobutyl group, a 1,2-dimethyl-cyclobutyl group, a 1,3-dimethyl-cyclobutyl group, a 2,2-dimethyl-cyclobutyl group, a 2,3-dimethyl-cyclobutyl group, a 2,4-dimethyl-cyclobutyl group, a 3,3-dicyclobutyl group, a cyclohexyl ... Examples of cycloalkyl groups include methyl-cyclobutyl group, 1-n-propyl-cyclopropyl group, 2-n-propyl-cyclopropyl group, 1-i-propyl-cyclopropyl group, 2-i-propyl-cyclopropyl group, 1,2,2-trimethyl-cyclopropyl group, 1,2,3-trimethyl-cyclopropyl group, 2,2,3-trimethyl-cyclopropyl group, 1-ethyl-2-methyl-cyclopropyl group, 2-ethyl-1-methyl-cyclopropyl group, 2-ethyl-2-methyl-cyclopropyl group, and 2-ethyl-3-methyl-cyclopropyl group; and bicycloalkyl groups such as bicyclobutyl group, bicyclopentyl group, bicyclohexyl group, bicycloheptyl group, bicyclooctyl group, bicyclononyl group, and bicyclodecyl group, but are not limited thereto. The number of carbon atoms is usually 3 to 14, preferably 4 to 10, and more preferably 5 to 6.

[0019] The alkenyl group may be either linear or branched, and the number of carbon atoms therein is not particularly limited, but is usually 2 to 40, preferably 30 or less, more preferably 20 or less, and even more preferably 10 or less.

[0020] Specific examples of the optionally substituted linear or branched alkenyl group include, but are not limited to, a vinyl group, an allyl group, a butenyl group, a pentenyl group, and the like, and the number of carbon atoms is usually 2 to 14, preferably 2 to 10, and more preferably 1 to 6. Among these, an ethenyl group and a 2-propenyl group are particularly preferred. Specific examples of the optionally substituted cyclic alkenyl group include, but are not limited to, cyclopentenyl, cyclohexenyl, and the like. The number of carbon atoms is usually 4 to 14, preferably 5 to 10, and more preferably 5 to 6.

[0021] As described above, polysiloxane (A1) contains polyorganosiloxane (a1') and polyorganosiloxane (a2'), and the alkenyl group contained in polyorganosiloxane (a1') and the hydrogen atom (Si-H group) contained in polyorganosiloxane (a2') form a crosslinked structure by hydrosilylation reaction with platinum group metal catalyst (A2), and are cured. As a result, a cured film is formed.

[0022] The polyorganosiloxane (a1') contains one or more units selected from the group consisting of Q' units, M' units, D' units and T' units, and also contains at least one unit selected from the group consisting of M' units, D' units and T' units. As the polyorganosiloxane (a1'), a combination of two or more polyorganosiloxanes satisfying such conditions may be used.

[0023] Preferred combinations of two or more selected from the group consisting of Q' units, M' units, D' units and T' units include, but are not limited to, (Q' units and M' units), (D' units and M' units), (T' units and M' units) and (Q' units, T' units and M' units).

[0024] In addition, when the polyorganosiloxane (a1') contains two or more types of polyorganosiloxane, combinations of (Q' units and M' units) and (D' units and M' units), combinations of (T' units and M' units) and (D' units and M' units), and combinations of (Q' units, T' units and M' units) and (T' units and M' units) are preferred, but are not limited to these.

[0025] The polyorganosiloxane (a2') contains one or more units selected from the group consisting of Q" units, M" units, D" units, and T" units, and also contains at least one unit selected from the group consisting of M" units, D" units, and T" units. As the polyorganosiloxane (a2'), a combination of two or more polyorganosiloxanes satisfying such conditions may be used.

[0026] Preferred combinations of two or more selected from the group consisting of Q″ units, M″ units, D″ units and T″ units include, but are not limited to, (M″ units and D″ units), (Q″ units and M″ units), and (Q″ units, T″ units and M″ units).

[0027] The polyorganosiloxane (a1') is composed of siloxane units having alkyl and / or alkenyl groups bonded to the silicon atoms thereof. 1 '~R 6 The proportion of alkenyl groups in all the substituents represented by R 1 '~R 6 ' can be an alkyl group.

[0028] The polyorganosiloxane (a2') is composed of siloxane units in which an alkyl group and / or a hydrogen atom is bonded to the silicon atom. 1 ”~R 6 The proportion of hydrogen atoms in all the substituents and substituted atoms represented by R 1 ”~R6 " can be an alkyl group.

[0029] When the component (A) contains (a1) and (a2), in a preferred embodiment of the present invention, the molar ratio of the alkenyl groups contained in the polyorganosiloxane (a1) to the hydrogen atoms constituting the Si-H bonds contained in the polyorganosiloxane (a2) is in the range of 1.0:0.5 to 1.0:0.66.

[0030] The weight average molecular weight of polysiloxanes such as polyorganosiloxane (a1) and polyorganosiloxane (a2) is not particularly limited, but is usually 500 to 1,000,000, and preferably 5,000 to 50,000 from the viewpoint of achieving the effects of the present invention with good reproducibility. In the present invention, the weight average molecular weight, number average molecular weight and dispersity of the polyorganosiloxane can be measured, for example, using a GPC apparatus (EcoSEC, HLC-8320GPC manufactured by Tosoh Corporation) and a GPC column (TSKgel SuperMultiporeHZ-N, TSKgel SuperMultiporeHZ-H manufactured by Tosoh Corporation), with a column temperature of 40°C, tetrahydrofuran as an eluent (elution solvent), a flow rate (flow rate) of 0.35 mL / min, and polystyrene (manufactured by Sigma-Aldrich) as a standard sample.

[0031] The viscosities of the polyorganosiloxane (a1) and the polyorganosiloxane (a2) are not particularly limited, but are usually 10 to 1,000,000 (mPa·s), and from the viewpoint of realizing the effects of the present invention with good reproducibility, are preferably 50 to 10,000 (mPa·s). The viscosities of the polyorganosiloxane (a1) and the polyorganosiloxane (a2) are values ​​measured at 25°C using an E-type rotational viscometer.

[0032] Polyorganosiloxane (a1) and polyorganosiloxane (a2) react with each other to form a film by hydrosilylation, and therefore the mechanism of cure is different from that via, for example, silanol groups, and therefore neither siloxane needs to contain silanol groups or functional groups that form silanol groups upon hydrolysis, such as alkyloxy groups.

[0033] In a preferred embodiment of the present invention, the thermosetting adhesive component comprises a platinum group metal catalyst (A2) together with the polyorganosiloxane component (A'). Such a platinum-based metal catalyst is a catalyst for promoting the hydrosilylation reaction between the alkenyl groups of the polyorganosiloxane (a1) and the Si-H groups of the polyorganosiloxane (a2).

[0034] Specific examples of platinum-based metal catalysts include platinum black, platinic chloride, chloroplatinic acid, a reaction product of chloroplatinic acid with a monohydric alcohol, a complex of chloroplatinic acid with an olefin, platinum bisacetoacetate, and other platinum-based catalysts, but are not limited to these. An example of a complex of platinum with an olefin is, but is not limited to, a complex of divinyltetramethyldisiloxane with platinum. The amount of the platinum group metal catalyst (A2) is not particularly limited, but is usually in the range of 1.0 to 50.0 ppm based on the total amount of the polyorganosiloxane (a1) and the polyorganosiloxane (a2).

[0035] The polyorganosiloxane component (A') may contain a polymerization inhibitor (A3) for the purpose of inhibiting the progress of the hydrosilylation reaction. The polymerization inhibitor is not particularly limited as long as it can inhibit the progress of the hydrosilylation reaction. Specific examples include alkynyl alcohols such as 1-ethynyl-1-cyclohexanol and 1,1-diphenyl-2-propion-1-ol. The amount of the polymerization inhibitor is not particularly limited, but is usually 1000.0 ppm or more based on the total amount of polyorganosiloxane (a1) and polyorganosiloxane (a2) from the viewpoint of obtaining the effect, and 10000.0 ppm or less from the viewpoint of preventing excessive inhibition of the hydrosilylation reaction.

[0036] An example of the thermosetting adhesive component used in the present invention may contain a component (B) that does not undergo a curing reaction to become a release agent component together with the curing component (A). By including such a component (B) in the thermosetting adhesive component, the resulting adhesive layer can be peeled off with good reproducibility. A typical example of such component (B) is a polyorganosiloxane, and specific examples thereof include, but are not limited to, epoxy group-containing polyorganosiloxane, methyl group-containing polyorganosiloxane, and phenyl group-containing polyorganosiloxane. In addition, the component (B) may be polydimethylsiloxane. The polydimethylsiloxane may be modified. Examples of the polydimethylsiloxane that may be modified include, but are not limited to, epoxy group-containing polydimethylsiloxane, unmodified polydimethylsiloxane, and phenyl group-containing polydimethylsiloxane.

[0037] Preferred examples of the polyorganosiloxane which is component (B) include, but are not limited to, epoxy group-containing polyorganosiloxanes, methyl group-containing polyorganosiloxanes, and phenyl group-containing polyorganosiloxanes.

[0038] The weight average molecular weight of the polyorganosiloxane, which is component (B), is not particularly limited, but is usually 100,000 to 2,000,000, and from the viewpoint of realizing the effects of the present invention with good reproducibility, it is preferably 200,000 to 1,200,000, and more preferably 300,000 to 900,000. The dispersity is not particularly limited, but is usually 1.0 to 10.0, and from the viewpoint of realizing suitable peeling with good reproducibility, it is preferably 1.5 to 5.0, and more preferably 2.0 to 3.0. The weight average molecular weight and dispersity can be measured by the above-mentioned method for polysiloxane. The viscosity of the polyorganosiloxane, which is component (B), is not particularly limited, but is usually 1,000 to 2,000,000 mm 2 The viscosity value of the polyorganosiloxane, which is component (B), is expressed as a kinematic viscosity, and is expressed as centistokes (cSt) = mm 2 / s. Viscosity (mPa s) is density (g / cm 3 That is, the value can be calculated from the viscosity and density measured with an E-type rotational viscometer at 25°C, and the kinematic viscosity (mm 2 / s)=viscosity (mPa s) / density (g / cm 3 ) can be calculated from the formula:

[0039] Examples of epoxy group-containing polyorganosiloxanes include R 11 R 12 SiO 2 / 2 The siloxane unit (D 10 Examples include those containing the unit.

[0040] R 11 is a group bonded to a silicon atom and represents an alkyl group; R 12 is a group bonded to a silicon atom, and represents an epoxy group or an organic group containing an epoxy group. Specific examples of the alkyl group include those listed above. The epoxy group in the epoxy group-containing organic group may be an independent epoxy group that is not condensed with other rings, or may be an epoxy group that forms a condensed ring with other rings, such as a 1,2-epoxycyclohexyl group. Specific examples of organic groups containing an epoxy group include, but are not limited to, 3-glycidoxypropyl and 2-(3,4-epoxycyclohexyl)ethyl. In the present invention, a preferred example of the epoxy group-containing polyorganosiloxane is epoxy group-containing polydimethylsiloxane, but is not limited thereto.

[0041] The epoxy group-containing polyorganosiloxane is a polyorganosiloxane having the above-mentioned siloxane unit (D 10 D 10 In addition to units, Q units, M units and / or T units may be included. In a preferred embodiment of the present invention, specific examples of the epoxy group-containing polyorganosiloxane include 10 Polyorganosiloxane consisting of only units, D 10 Polyorganosiloxanes containing D units and Q units; 10 Polyorganosiloxanes containing D units and M units; 10 Polyorganosiloxanes containing D units and T units; 10 Polyorganosiloxanes containing units, Q units and M units, D 10 Polyorganosiloxanes containing units, M units and T units, D 10 and polyorganosiloxanes containing Q units, M units and T units.

[0042] The epoxy group-containing polyorganosiloxane is preferably an epoxy group-containing polydimethylsiloxane having an epoxy value of 0.1 to 5. In addition, the weight average molecular weight is not particularly limited, but is usually 1,500 to 500,000, and from the viewpoint of suppressing precipitation in the adhesive, is preferably 100,000 or less.

[0043] Specific examples of the epoxy group-containing polyorganosiloxane include those represented by formulas (E1) to (E3), but are not limited thereto.

[0044] [ka] (m1 and n1 each represent the number of repeating units and are positive integers.)

[0045] [ka] (m2 and n2 each represent the number of repeating units and are positive integers, and R represents an alkylene group having 1 to 10 carbon atoms.)

[0046] [ka] (m3, n3, and o3 each represent the number of repeating units and are positive integers, and R represents an alkylene group having 1 to 10 carbon atoms.)

[0047] Examples of the methyl group-containing polyorganosiloxane include R 210 R 220 SiO 2 / 2 The siloxane unit (D 200 units), preferably R 21 R 21 SiO 2 / 2 The siloxane unit (D 20 Examples include those containing the unit.

[0048] R 210 and R 220 are groups bonded to a silicon atom, and each independently represents an alkyl group, with at least one being a methyl group. Specific examples of the alkyl group include those listed above. R 21 is a group bonded to a silicon atom, and represents an alkyl group. Specific examples of the alkyl group include those listed above. 21 As the alkyl group, a methyl group is preferable. In the present invention, a preferred example of the methyl group-containing polyorganosiloxane is polydimethylsiloxane, but is not limited thereto.

[0049] The methyl group-containing polyorganosiloxane is a polyorganosiloxane having the above-mentioned siloxane unit (D 200 Unit or D 20 D 200 Units and D 20 In addition to units, Q units, M units and / or T units may be included.

[0050] In one embodiment of the present invention, specific examples of the methyl group-containing polyorganosiloxane include D 200 Polyorganosiloxane consisting of only units, D 200 Polyorganosiloxanes containing D units and Q units; 200 Polyorganosiloxanes containing D units and M units; 200 Polyorganosiloxanes containing D units and T units; 200 Polyorganosiloxanes containing units, Q units and M units, D 200 Polyorganosiloxanes containing units, M units and T units, D 200 Examples of suitable polyorganosiloxanes include polyorganosiloxanes containing Q, M, and T units.

[0051] In a preferred embodiment of the present invention, specific examples of the methyl group-containing polyorganosiloxane include D 20 Polyorganosiloxane consisting of only units, D 20 Polyorganosiloxanes containing D units and Q units; 20 Polyorganosiloxanes containing D units and M units; 20 Polyorganosiloxanes containing D units and T units; 20 Polyorganosiloxanes containing units, Q units and M units, D 20 Polyorganosiloxanes containing units, M units and T units, D 20 Examples of suitable polyorganosiloxanes include polyorganosiloxanes containing Q, M, and T units.

[0052] Specific examples of methyl group-containing polyorganosiloxanes include, but are not limited to, those represented by formula (M1).

[0053] [ka] (n4 represents the number of repeating units and is a positive integer.)

[0054] Examples of the phenyl group-containing polyorganosiloxane include R 31 R 32 SiO 2 / 2 The siloxane unit (D 30 Examples include those containing the unit.

[0055] R 31 is a group bonded to a silicon atom and represents a phenyl group or an alkyl group; R 32 is a group bonded to a silicon atom and represents a phenyl group. Specific examples of the alkyl group include those listed above, with a methyl group being preferred.

[0056] The phenyl group-containing polyorganosiloxane is a polyorganosiloxane having the above-mentioned siloxane unit (D 30 D 30 In addition to units, Q units, M units and / or T units may be included.

[0057] In a preferred embodiment of the present invention, specific examples of the phenyl group-containing polyorganosiloxane include D 30 Polyorganosiloxane consisting of only units, D 30 Polyorganosiloxanes containing D units and Q units; 30 Polyorganosiloxanes containing D units and M units; 30 Polyorganosiloxanes containing D units and T units; 30 Polyorganosiloxanes containing units, Q units and M units, D 30 Polyorganosiloxanes containing units, M units and T units, D 30 Examples of suitable polyorganosiloxanes include polyorganosiloxanes containing Q, M, and T units.

[0058] Specific examples of the phenyl group-containing polyorganosiloxane include those represented by formula (P1) or (P2), but are not limited thereto.

[0059] [ka] (m5 and n5 each represent the number of repeating units and are positive integers.)

[0060] [ka] (m6 and n6 each represent the number of repeating units and are positive integers.)

[0061] In one embodiment, the thermosetting adhesive component used in the present invention contains a component (A) that cures and a component (B) that does not undergo a curing reaction, and in a more preferred embodiment, component (B) contains a polyorganosiloxane.

[0062] An example of the thermosetting adhesive component used in the present invention can contain component (A) and component (B) in any ratio. Taking into consideration the balance between adhesion and peelability, the ratio of component (A) to component (B) in terms of mass ratio [(A):(B)] is preferably 99.995:0.005 to 30:70, and more preferably 99.9:0.1 to 75:25. That is, when the composition contains a polyorganosiloxane component (A') that cures by a hydrosilylation reaction, the mass ratio of component (A') to component (B) [(A'):(B)] is preferably 99.995:0.005 to 30:70, and more preferably 99.9:0.1 to 75:25.

[0063] The viscosity of the thermosetting adhesive component used in the present invention is not particularly limited, but is usually 500 to 20,000 mPa·s at 25°C, and preferably 1,000 to 1,0000 mPa·s.

[0064] In the present invention, the curing initiation temperature Tc (° C.) of the thermosetting adhesive component can be measured by the following method. 5 mg of the thermosetting adhesive component is weighed out onto an aluminum pan, and the calorific value is measured using a DSC (e.g., a differential scanning calorimeter Q-2000 from TA Instruments, Inc.), with the calorific value plotted on the vertical axis and temperature on the horizontal axis, and the temperature at which the peak of the calorific value is confirmed can be obtained as the curing start temperature Tc (°C) of the thermosetting adhesive component. Note that the temperature rise condition at this time can be, for example, 10°C / min from room temperature (23°C) to 300°C.

[0065] <Thermal expansion particles> The adhesive composition of the present invention contains thermally expandable particles in an amount of 3.5 mass % or less based on the thermosetting adhesive component. For example, thermally expandable particles are microcapsules that contain a volatile material encapsulated within a shell composed of a thermoplastic resin, and that expand when heated. Specifically, for example, a microcapsule (shell) having a thickness of 2 to 15 μm encapsulates an organic solvent that is a swelling agent (volatile substance). Thermoplastic resins forming the shell of this component include, for example, vinyl polymers such as polyethylene, polystyrene, polyvinyl acetate, polyvinyl chloride, polyvinylidene chloride, polyacrylonitrile, polymethyl methacrylate, polybutadiene, polychloroprene, and copolymers thereof; polyamides such as nylon 6 and nylon 66; and polyethylene terephthalate, polyacetal, and blends thereof. Among these, vinyl polymers such as polyethylene, polystyrene, polyvinyl acetate, polyvinyl chloride, polyvinylidene chloride, polyacrylonitrile, polymethyl methacrylate, polybutadiene, and polychloroprene, and copolymers thereof are preferred because they mix well with organic solvents and thermosetting adhesive components, and polyacrylonitrile-based copolymers are more preferred. Examples of volatile substances encapsulated in the thermally expandable particles include organic solvents such as hydrocarbons such as butane, isobutene, and propane; alcohols such as methanol and ethanol; halogenated hydrocarbons such as dichloroethane, trichloroethane, and trichloroethylene; and ethers such as diethyl ether and isopropyl ether. Among these, hydrocarbons are preferred because they contribute to good stability within the capsule and excellent thermal expandability. The volatile matter in the capsule is typically 1.01 x 10 5 It is liquid at 25°C and 32 Pa.

[0066] The shape of the thermally expandable particles is not particularly limited and can be appropriately selected depending on the purpose. Examples of the shape include spherical, acicular, and amorphous shapes, but the shape is usually spherical.

[0067] The maximum expansion ratio of the heat-expandable particles is appropriately set taking into consideration other physical properties of the heat-expandable particles so as to obtain porosity sufficient to reduce the adhesive strength required for peeling, but is greater than 1, and in one embodiment, is 3 to 15 from the viewpoint of achieving good peelability with good reproducibility.

[0068] The average particle size of the thermally expandable particles before expansion is not particularly limited as long as it is smaller than the thickness of the adhesive layer to be formed and is well mixed with the adhesive components, but is usually 3 to 100 μm, and in one embodiment, 5 to 50 μm. In the present invention, the average particle size of the thermally expandable particles can be obtained as the average particle size of the D50 value using a particle size distribution analyzer (for example, a laser diffraction particle size distribution analyzer SALD-3100 manufactured by Shimadzu Corporation).

[0069] The expansion start temperature Ts (°C) of the thermally expandable particles can be measured, for example, by the following method. Using a dynamic mechanical analysis (DMA) (e.g., DMA Q800 manufactured by TA Instruments), 0.5 mg of particles is placed in an aluminum cup with a diameter of 6.0 mm (inner diameter 5.65 mm) and a depth of 4.8 mm, and an aluminum lid (diameter 5.6 mm, thickness 0.1 mm) is placed on the top of the particle layer to prepare a measurement sample, and the height of the measurement sample is measured while a force of 0.01 N is applied from above with a pressure bar, and the measurement sample is heated from 20°C to 300°C at a heating rate of 10°C / min while a force of 0.01 N is applied with the pressure bar, and the displacement of the pressure bar in the vertical direction is measured, whereby the expansion start temperature (Ts) can be obtained as the temperature at which the displacement in the positive direction begins, and the maximum expansion temperature (Tm) can be obtained as the temperature at which the maximum displacement is observed. The expansion starting temperature (° C.) of the thermally expandable particles is preferably 50 to 120° C. from the viewpoint of realizing good peeling with good reproducibility.

[0070] In the present invention, the maximum expansion ratio Ms of the thermally expandable particles is based on the true gravity of the thermally expandable particles at "maximum expansion", and when the average true specific gravity of the particle group before thermal expansion is Db and the average true specific gravity when the particle group is heated to expand and the average true specific gravity becomes minimum is Da, the maximum expansion ratio of the thermally expandable particles is expressed as Db / Da (times). In other words, the maximum expansion ratio can be calculated using the true specific gravity Db of the thermally expansive particles and the true specific gravity Da of the thermally expansive particles after heating (expanding). The true specific gravity can be measured by the immersion method (Archimedes method) using isopropyl alcohol in an atmosphere with an environmental temperature of 25°C and a relative humidity of 50%. The heating conditions are as follows: 1 g of heat-expandable particles is heated in an oven for 2 minutes at each temperature in the range from the expansion start temperature (Ts) to a temperature 100°C higher than the maximum expansion temperature (Tm); the maximum expansion that gives the lowest true specific gravity value Df is defined as the maximum expansion; and the maximum expansion ratio Ms of the heat-expandable particles is calculated using the formula Ms = (Db ÷ Df).

[0071] The thermally expandable particles can be produced by known methods (e.g., WO2020 / 017361, WO2019 / 150951, WO2019 / 124233, WO2018 / 092554, WO2017 / 141653, WO2017 / 002659, WO2016 / 190178, WO2016 / 140080, WO2016 / 084612, WO2015 / 178329, JP 2016-169274, JP 2015-129290, WO2015 / 098586, WO2015 / 060086, WO2015 / 029916, JP 2015-3951, WO2013 / 111688, JP 2013-173945, JP 2012-136695, JP 2012-17453, JP 2011-195813, JP 2012-144820, JP 2012-122025, JP 2011-32626, JP 2011-256224, WO2010 / 143512, JP 2011-68890, WO2009 / 050863, WO2008 / 142 849, JP 2008-291067, WO2007 / 058379, WO2007 / 046273, JP 2006-213930, WO2005 / 049698, JP 2004-323854, WO2004 / 074396, WO2004 / 058910, JP 2015-108153, JP 2014-169443, JP 2013-28818, JP 2013-32542, JP 2009-299071, JP 2009-113037, WO2003 / 09 9955, WO2001 / 072410, WO2001 / 023081, WO1999 / 046320, WO1999 / 043758, JP 2000-24488, JP 11-2615, JP 5-329360, JP 5-309262, JP 5-285376, JP 9-19635, JP 62-286534, JP 59-173132, JP 56-113338, etc.), or they can be obtained as a commercially available product.Such commercially available products include Matsumoto Microsphere (registered trademark) F-30, HF-30D, F-35, F-35D, HF-36, HF-36D, F-36LV, F-36LVD, HF-48, HF-48D, FN-80GS, FN-80GSD, HF-50, F-50D, F-65, F-65D, FN-100SS, FN-100SSD, FN-100S, FN-100SD, F-100M, F-100D ... Examples of such disks include, but are not limited to, FN-00MD, FN-78, FN-78D, FN-100M, FN-100MD, FN-105, FN-105D, FN-180SS, FN-180SSD, FN-180S, FN-180SD, FN-180, FN-180D, FN-190SSD, F-190D, F-260D, F-2800D, F-2830D, and F-2860D.

[0072] In the present invention, the content of the thermally expandable particles is 3.5% by mass or less, preferably 3.4% by mass or less, more preferably 3.3% by mass or less, even more preferably 3.2% by mass or less, and even more preferably 3.1% by mass or less, based on the thermosetting adhesive component, from the viewpoint of achieving both the peelability of the adhesive layer and the storage stability of the adhesive composition. The lower limit of the content of the thermally expandable particles is not particularly limited as long as it generates an amount of gas that contributes to porosity that can realize the reduction in adhesive ability required for peeling, but is usually 0.05% by mass, preferably 0.1% by mass, based on the thermosetting adhesive component. Since the adhesive composition of the present invention contains a predetermined amount of heat-expanding particles, during the process of heating the adhesive coating layer and curing the thermosetting adhesive component to produce the adhesive layer, gas is generated from the heat-expanding particles, which results in the layer curing in a state in which voids (porosity) are generated in the layer, and these voids cause a decrease in the adhesive ability of the adhesive layer compared to a case in which there are no voids, resulting in good releasability. At the same time, since the amount of heat-expanding particles is suitably adjusted, the adhesive composition has excellent storage stability. The porosity of the adhesive layer can be observed with an optical microscope, and if no porosity is observed at all, peeling is not possible, so part of the adhesive layer must be made porous.

[0073] <Other ingredients> The adhesive composition used in the present invention may contain a solvent for the purpose of adjusting the viscosity, etc. Specific examples of the solvent include, but are not limited to, aliphatic hydrocarbons, aromatic hydrocarbons, ketones, etc.

[0074] More specifically, examples of the solvent include, but are not limited to, hexane, heptane, octane, nonane, decane, undecane, dodecane, isododecane, menthane, limonene, toluene, xylene, mesitylene, cumene, MIBK (methyl isobutyl ketone), butyl acetate, diisobutyl ketone, 2-octanone, 2-nonanone, 5-nonanone, etc. Such solvents may be used alone or in combination of two or more.

[0075] When the adhesive composition used in the present invention contains a solvent, the content of the solvent is appropriately set taking into consideration the desired viscosity of the composition, the coating method to be used, the thickness of the film to be produced, etc., but is in the range of about 10 to 90 mass % of the entire composition.

[0076] The viscosity of the adhesive composition used in the present invention is not particularly limited, but is usually 500 to 20,000 mPa·s, and preferably 1,000 to 10,000 mPa·s at 25° C. The viscosity of the adhesive composition used in the present invention can be adjusted by changing the types of solvents used, their ratios, the concentrations of the film constituent components, etc., taking into consideration various factors such as the coating method used and the desired film thickness.

[0077] It is preferable that the adhesive composition of the present invention has a uniform mixture of the components therein and that the composition has sufficient fluidity to enable application. For the purpose of achieving this or for the purpose of adjusting the viscosity, surface tension, etc. of the composition, the adhesive composition may contain a solvent. However, when the adhesive composition is composed only of a thermosetting adhesive component and thermally expandable particles, the adhesive composition of the present invention does not necessarily need to contain a solvent as long as the adhesive composition has at least sufficient fluidity to enable application, and preferably further has the components uniformly mixed.

[0078] <Method of manufacturing adhesive composition> In a preferred embodiment of the method for producing the adhesive composition, for example, the adhesive composition of the present invention can be produced by mixing a thermosetting adhesive component and a thermally expandable particle. The order of mixing is not particularly limited. In the present invention, for the purpose of removing foreign matter, the solvent, solution, etc. used may be filtered using a filter during the production of the adhesive composition or after all of the components have been mixed.

[0079] (Laminate) The laminate of the present invention comprises a semiconductor substrate, a support substrate, and an adhesive layer. The adhesive layer is interposed between the semiconductor substrate and the support substrate and is in contact with the semiconductor substrate. The adhesive layer is a layer formed from the adhesive composition of the present invention described above. The laminate is used for temporarily bonding a semiconductor substrate for processing, and is used in applications in which the support substrate and the semiconductor substrate are separated from each other after processing of the semiconductor substrate in the laminate. In the laminate of the present invention, the number of adhesive layers is not particularly limited and may be appropriately selected depending on the purpose. For example, the laminate may have one adhesive layer or two or more adhesive layers. A preferred embodiment of the laminate of the present invention is a laminate having a second adhesive layer formed using a second adhesive composition that does not contain thermally expandable particles, in addition to the adhesive layer made of the adhesive composition of the present invention. In this case, the laminate has a semiconductor substrate, an adhesive layer made of the adhesive composition of the present invention, a second adhesive layer made of the second adhesive composition that does not contain thermally expandable particles, and a support substrate. The laminate including the second adhesive layer is preferably laminated in the order of the semiconductor substrate, the adhesive layer, the second adhesive layer, and the support substrate.

[0080] As shown in the following examples, the laminate of the present invention satisfies the peelability that the adhesive layer peels off when the semiconductor substrate and the support substrate are separated, and the semiconductor substrate can be easily peeled off from the adhesive layer. Furthermore, as shown in the following examples, the laminate of the present invention has an adhesive layer formed using an adhesive composition with good storage stability. By forming the adhesive layer using an adhesive composition with good storage stability, an adhesive layer with good performance can be stably produced, and a laminate with guaranteed quality stability of the adhesive layer can be obtained. Therefore, the laminate of the present invention is a laminate that is satisfactory in terms of both releasability and quality stability.

[0081] An example of the laminate will be described below with reference to the drawings. FIG. 1A is a schematic cross-sectional view of an example of a laminate. In addition, in FIG. 1A (as well as FIG. 1B), an example will be described in which a semiconductor substrate with bumps is used as the semiconductor substrate. The laminate in FIG. 1A includes a semiconductor substrate 1 having bumps 1a, an adhesive layer 2, and a support substrate 4, in this order. The bumps 1a of the semiconductor substrate 1 are disposed on the support substrate 4 side. The adhesive layer 2 is interposed between the semiconductor substrate 1 and the support substrate 4. The adhesive layer 2 is in contact with the semiconductor substrate 1. The adhesive layer 2 covers the bumps 1a. FIG. 1B is a schematic cross-sectional view of another example of the laminate. The laminate in FIG. 1B includes a semiconductor substrate 1 having bumps 1a, an adhesive layer 2, a second adhesive layer 3, and a support substrate 4 in this order. The bumps 1a of the semiconductor substrate 1 are disposed on the support substrate 4 side. The adhesive layer 2 is interposed between the semiconductor substrate 1 and the support substrate 4. The adhesive layer 2 is in contact with the semiconductor substrate 1. The adhesive layer 2 covers the bumps 1a. The second adhesive layer 3 is interposed between the adhesive layer 2 and the supporting substrate 4. The second adhesive layer 3 is in contact with the adhesive layer 2 and the supporting substrate 4. Each component of the laminate of the present invention will be described in detail below.

[0082] <Semiconductor substrate> The semiconductor substrate may have bumps, which are protruding terminals. When the semiconductor substrate used has bumps, the semiconductor substrate has the bumps on the supporting substrate side in the laminate. In a semiconductor substrate, bumps are usually formed on a surface on which a circuit is formed. The circuit may be a single layer or a multilayer. There is no particular limitation on the shape of the circuit. In the semiconductor substrate, the surface opposite to the surface having the bumps (back surface) is the surface to be processed.

[0083] The main material constituting the entire semiconductor substrate is not particularly limited as long as it is used for this type of application, but examples thereof include silicon, silicon carbide, and compound semiconductors. The shape of the semiconductor substrate is not particularly limited, but may be, for example, a disk shape. Note that the disk-shaped semiconductor substrate does not need to have a perfectly circular surface, and for example, the outer periphery of the semiconductor substrate may have a straight line portion called an orientation flat, or may have a cut called a notch. The thickness of the disk-shaped semiconductor substrate may be appropriately determined depending on the intended use of the semiconductor substrate, and is not particularly limited, but is, for example, 500 to 1,000 μm. The diameter of the disk-shaped semiconductor substrate may be appropriately determined depending on the intended use of the semiconductor substrate, and is not particularly limited, but may be, for example, 100 to 1,000 mm.

[0084] An example of a semiconductor substrate is a silicon wafer having a diameter of about 300 mm and a thickness of about 770 μm.

[0085] The material, size, shape, structure, and density of the bumps on the semiconductor substrate are not particularly limited. Examples of the bump include a ball bump, a printed bump, a stud bump, and a plated bump. Usually, the height, diameter and pitch of the bumps are appropriately determined based on the conditions of a bump height of about 1 to 200 μm, a bump diameter of 1 to 200 μm and a bump pitch of 1 to 500 μm. Examples of materials for the bump include low melting point solder, high melting point solder, tin, indium, gold, silver, copper, etc. The bump may be composed of only a single component, or may be composed of multiple components. More specifically, examples of the bump include alloy plating mainly composed of Sn, such as SnAg bump, SnBi bump, Sn bump, and AuSn bump. The bump may have a laminated structure including a metal layer made of at least one of these components.

[0086] <Support substrate> The support substrate is not particularly limited as long as it is a member capable of supporting a semiconductor substrate when the semiconductor substrate is processed, and examples thereof include a glass support substrate and a silicon support substrate.

[0087] The shape of the support substrate is not particularly limited, and may be, for example, a disk shape. Note that the shape of the surface of the disk-shaped support substrate does not need to be a perfect circle, and for example, the outer periphery of the support substrate may have a straight line portion called an orientation flat, or may have a cut called a notch. The thickness of the disk-shaped support substrate may be appropriately determined depending on the size of the semiconductor substrate, and is not particularly limited, but is, for example, 500 to 1,000 μm. The diameter of the disk-shaped support substrate may be appropriately determined depending on the size of the semiconductor substrate, and is not particularly limited, but is, for example, 100 to 1,000 mm.

[0088] An example of the support substrate is a glass wafer or a silicon wafer having a diameter of about 300 mm and a thickness of about 700 μmm.

[0089] <Adhesive layer> The adhesion layer is interposed between the support substrate and the semiconductor substrate. The adhesion layer is in contact with the semiconductor substrate.

[0090] The adhesive layer is formed using the above-mentioned adhesive composition of the present invention, more specifically, by curing the adhesive composition. The thickness of the adhesive layer is not particularly limited, but from the viewpoint of obtaining good releasability, it is preferably 0.1 to 30 μm, and more preferably 1 to 10 μm. In particular, when the adhesive layer in the laminate consists only of an adhesive layer formed using the adhesive composition of the present invention, the thickness of the adhesive layer is preferably 10 to 70 μm, more preferably 30 to 60 μm. On the other hand, when the adhesive layer in the laminate includes a second adhesive layer in addition to the adhesive layer formed using the adhesive composition of the present invention, the thickness of the adhesive layer is preferably 0.1 to 30 μm, more preferably 1 to 10 μm. The method for forming an adhesive layer from the adhesive composition will be described in detail in the section below on <Method for producing a laminate>.

[0091] <Second adhesive layer> The laminate of the present invention may also include a second adhesive layer. When the laminate has a second adhesive layer, the second adhesive layer is interposed between the supporting substrate and the adhesive layer. The second adhesive layer is preferably in contact with the supporting substrate and the adhesive layer.

[0092] The second adhesive layer is formed by using a second adhesive composition, and more specifically, by curing the second adhesive composition. The second adhesive composition includes a thermosetting adhesive component, with the exception that the second adhesive composition does not include thermally expandable particles. The thermosetting adhesive component contained in the second adhesive composition is not particularly limited, but the same thermosetting adhesive component as that described above can be used as the thermosetting adhesive component contained in the adhesive composition of the present invention, as described in the <Thermosetting Adhesive Component> section of the above (Adhesive Composition), and other thermosetting adhesive components described below can also be used. The amount and suitable conditions of the thermosetting adhesive component contained in the second adhesive composition are also the same as those described above for the adhesive composition. The thermosetting adhesive component contained in the adhesive composition and the thermosetting adhesive component contained in the second adhesive composition may be the same type of thermosetting adhesive component or different types of thermosetting adhesive components. The second adhesive composition may contain, in addition to the thermosetting adhesive component, other components such as a solvent, as in the adhesive composition of the present invention, and the amounts and suitable conditions for these are the same as those described above.

[0093] The thickness of the second adhesive layer provided in the laminate of the present invention is not particularly limited, but is usually 5 to 500 μm, and from the viewpoint of maintaining film strength, it is preferably 10 μm or more, more preferably 20 μm or more, and even more preferably 30 μm or more, and from the viewpoint of avoiding non-uniformity due to a thick film, it is preferably 200 μm or less, more preferably 150 μm or less, even more preferably 120 μm or less, and even more preferably 70 μm or less.

[0094] The film thickness ratio of the adhesive layer and the second adhesive layer in the laminate of the present invention is not particularly limited, but from the viewpoint of reproducibly obtaining a laminate having good peelability and electrode (bump) protection properties, the thickness of the second adhesive layer is usually 0.5 to 30, preferably 1 to 20, more preferably 2 to 15, even more preferably 3 to 10, and even more preferably 4 to 8, relative to the thickness of the adhesive layer.

[0095] <<Other thermosetting adhesive components>> The second adhesive composition may contain, as the thermosetting adhesive component, for example, a curable adhesive material described below, or the curable adhesive material and a release additive. The curable adhesive material may be selected from, for example, polyarylene oligomers, cyclic olefin oligomers, arylcyclobutene oligomers, vinyl aromatic oligomers, and mixtures thereof. Release additives include, for example, polyether compounds. It is preferred that the polyether compound comprises end groups selected from the group consisting of hydroxy, alkoxy, aryloxy, and mixtures thereof. It is preferred that the polyether compound is selected from polyethylene glycol, polypropylene glycol, poly(1,3-propanediol), polybutylene glycol, poly(tetrahydrofuran), ethylene glycol-propylene glycol copolymers, and mixtures thereof. It is preferred that the release additive is selected from the group consisting of polyalkylene oxide homopolymers and polyalkylene oxide copolymers. As the thermosetting adhesive component, for example, the temporary bonding composition described in JP 2014-150239 A can be used. The thermosetting adhesive components are described in further detail below.

[0096] The thermosetting adhesive component includes a curable adhesive material and a release additive. Typically, the curable adhesive material has a modulus of >1 GPa when cured. Exemplary curable adhesive materials include, but are not limited to, polyarylene oligomers, cyclic olefin oligomers, arylcyclobutene oligomers, vinyl aromatic oligomers, and mixtures thereof. The curable adhesive material may be substituted with any suitable moiety, such as fluorine-containing groups, to provide additional hydrophobicity, provided such moieties do not adversely affect the mechanical properties of the cured adhesive material. Preferably, the curable adhesive material is selected from polyarylene oligomers, cyclic olefin oligomers, arylcyclobutene oligomers, vinyl aromatic oligomers, and mixtures thereof, more preferably one or more of arylcyclobutene oligomers, vinyl aromatic oligomers, or mixtures thereof. When a mixture of different curable adhesive materials is used in the present invention, such materials are selected to cure together during the curing process. If a mixture of different curable materials is used, then these are used in a weight ratio of 99:1 to 1:99, preferably 95:5 to 5:95, more preferably 90:10 to 10:90, even more preferably 75:25 to 25:75.

[0097] A wide variety of polyarylene oligomers may be used in the present invention. As used herein, the term "polyarylene" includes polyarylene ethers. Suitable polyarylene oligomers may be synthesized from precursors, such as ethynyl aromatic compounds of the formula:

[0098] [ka] where each Ar is an aromatic group or an inertly substituted aromatic group; each R is independently hydrogen, alkyl, aryl, or an inertly substituted alkyl or aryl group; L is a covalent bond or a group linking one Ar to at least one other Ar; n and m are integers of at least 2; and q is an integer of at least 1. As such, ethynyl aromatic compounds typically have four or more ethynyl groups (e.g., tetraethynyl aromatic compounds).

[0099] Suitable polyarylene oligomers for use in the temporary bonding composition as the thermosetting adhesive component may include polymers that contain, as polymerized units:

[0100] [ka] where Ar' is the residue of the (C≡C)n-Ar or Ar-(C≡C)m portion of the reaction product, and R, L, n, and m are as defined above. Polyarylene copolymers useful in the present invention include, as polymerized units, monomers having the following formula:

[0101] [ka] In the formula, Ar′ and R are as defined above.

[0102] Exemplary polyarylenes include those where Ar-L-Ar is: biphenyl; 2,2-diphenylpropane; 9,9'-diphenylfluorene; 2,2-diphenylhexafluoropropane; diphenyl sulfide; oxydiphenylene; diphenyl ether; bis(phenylene)diphenylsilane; bis(phenylene)phosphine oxide; bis(phenylene)benzene; bis(phenylene)naphthalene; bis(phenylene)anthracene; thiodiphenylene; 1,1,1-triphenyleneethane; 1,3,5-triphenylenebenzene; 1,3,5-(2-phenylene-2-propyl)benzene; 1,1,1-triphenylenemethane; 1,1 , 2,2-tetraphenylene-1,2-diphenylethane; bis(1,1-diphenyleneethyl)benzene; 2,2'-diphenylene-1,1,1,3,3,3-hexafluoropropane; 1,1-diphenylene-1-phenylethane; naphthalene; anthracene; or bis(phenylene)naphthacene; more preferably biphenylene; naphthylene; p,p'-(2,2-diphenylenepropane) (or CH-C(CH)-CH-); p,p'-(2,2-diphenylene-1,1,1,3,3,3 hexafluoropropene) and (-CH-C(CF)-CH-). Useful bisphenyl derivatives include 2,2-diphenylpropane; 9,9'-diphenylfluorene; 2,2-diphenylhexafluoropropane; diphenyl sulfide; diphenyl ether; bis(phenylene)diphenylsilane; bis(phenylene)phosphine oxide; bis(phenylene)benzene; bis(phenylene)naphthalene; bis(phenylene)anthracene; or bis(phenylene)naphthacene.

[0103] Polyarylene precursor monomers can be prepared by a variety of methods known in the art, such as (a) selectively halogenating, preferably brominating, a polyphenol (preferably a bisphenol) in a solvent, where each phenolic ring is halogenated with one halogen at one of the two positions ortho to the phenolic hydroxyl group, and (b) converting the phenolic hydroxyls on the resulting poly(ortho-halophenols) to leaving groups (e.g., sulfonate esters) that are reactive with and displaced by terminal ethynyl compounds, preferably in a solvent. For example, trifluoromethanesulfonate esters prepared from trifluoromethanesulfonyl halide or trifluoromethanesulfonic anhydride; and (c) reacting the reaction product of step (b) with an ethynyl-containing compound or ethynyl synthon in the presence of an aryl ethynylation catalyst, preferably a palladium catalyst, and an acid acceptor to simultaneously replace the halogen and trifluoromethylsulfonate with an ethynyl-containing group (e.g., acetylene, phenylacetylene, substituted phenylacetylene, or substituted acetylene). Further description of this synthesis is provided in International Publication WO 97 / 10193 (Babb).

[0104] The ethynyl aromatic monomer of formula (I) is useful for preparing the polymer of either formula (II) or (III). Polymerization of ethynyl aromatic monomer is well within the ability of those skilled in the art. The specific conditions of polymerization depend on various factors, including the specific ethynyl aromatic monomer(s) to be polymerized and the desired properties of the resulting polymer, but the general conditions of polymerization are detailed in International Publication No. WO 97 / 10193 (Babb).

[0105] Particularly suitable polyarylenes for use in the present invention include those sold as SiLK™ semiconductor dielectrics (available from Dow Electronic Materials, Marlborough, Mass.). Other particularly suitable polyarylenes include those disclosed in WO 00 / 31183, WO 98 / 11149, WO 97 / 10193, WO 91 / 09081, European Patent Application Publication No. 755957, and U.S. Patent Nos. 5,115,082; 5,155,175; 5,179,188; 5,874,516; and 6,093,636.

[0106] A suitable cyclic olefin material is a poly(cyclic olefin), which may be thermoplastic and may have a weight average molecular weight (Mw) of preferably 2000 to 200,000 Daltons, more preferably 5000 to 100,000 Daltons, and even more preferably 2000 to 50,000 Daltons. A preferred poly(cyclic olefin) has a softening temperature (melt viscosity at 3,000 PaS) of at least 100°C, more preferably at least 140°C. A suitable poly(cyclic olefin) also has a glass transition temperature (Tg) of preferably at least 60°C, more preferably 60 to 200°C, and most preferably 75 to 160°C.

[0107] Preferred poly(cyclic olefins) comprise repeating monomers of cyclic and non-cyclic olefins, or ring-opened polymers based on cyclic olefins. Cyclic olefins suitable for use in the present invention are selected from norbornene-based olefins, tetracyclododecene-based olefins, dicyclopentadiene-based olefins, Diels-Alder polymers such as those derived from furans and maleimides, and derivatives thereof. Derivatives include alkyl (preferably C1-C 20 Alkyl, more preferably C1-C 10 alkyl), alkylidene (preferably C1-C 20 Alkylidene, more preferably C1-C 10 Alkylidene), aralkyl (preferably C6-C 30Aralkyl, more preferably C6-C 18 aralkyl), cycloalkyl (preferably C3-C 30 Cycloalkyl, more preferably C3-C 18 Cycloalkyl), ether, acetyl, aromatic, ester, hydroxy, alkoxy, cyano, amide, imide, and silyl-substituted derivatives. Particularly preferred cyclic olefins for use in the present invention include those selected from the following and combinations thereof:

[0108] [ka]

[0109] [ka] In the formula, each R 1 and R 2 are independently H and an alkyl group (preferably C1-C 20 Alkyl, more preferably C1-C 10 alkyl), and each R 3 are independently H, substituted and unsubstituted aryl groups (preferably C6-C 18 aryl), alkyl group (preferably C1-C 20 Alkyl, more preferably C1-C 10 alkyl), cycloalkyl groups (preferably C3-C 30 Cycloalkyl groups, more preferably C3-C 18 Cycloalkyl groups, aralkyl groups (preferably C6-C 30 Aralkyl, more preferably C6-C 18 Aralkyl groups, such as benzyl, phenethyl, phenylpropyl, etc., ester groups, ether groups, acetyl groups, alcohols (preferably C1-C 10 alcohols), aldehyde groups, ketones, nitriles, and combinations thereof.

[0110] Preferred acyclic olefins are branched and unbranched C2-C 20Alkenes (preferably C2-C 10 More preferably, the acyclic olefin is selected from the group consisting of the structure (R 4 )2C=C(R 4 )2, where each R 4 are independently H and an alkyl group (preferably C1-C 20 Alkyl, more preferably C1-C 10 Particularly preferred acyclic olefins for use in the present invention include those selected from ethene, propene and butene, with ethene being most preferred.

[0111] Methods for producing cyclic olefin copolymers are known in the art. For example, cyclic olefin copolymers can be produced by chain polymerization of cyclic and non-cyclic monomers. When norbornene is reacted with ethene under these conditions, ethene-norbornene copolymers containing alternating norbornanediyl and ethylene units are obtained. Examples of copolymers produced by this method include those available under the TOPAS™ (manufactured by Topas Advanced Polymers) and APEL™ (manufactured by Mitsui Chemicals, Inc.) brands. A suitable method for producing these copolymers is disclosed in U.S. Pat. No. 6,008,298. Cycloolefin copolymers can also be produced by ring-opening metathesis polymerization of various cyclic monomers followed by hydrogenation. The polymer resulting from this type of polymerization can be conceptualized as a copolymer of ethene and cyclic olefin monomers (e.g., alternating units of ethylene and cyclopentane-1,3-diyl). Examples of copolymers made by this ring-opening method include those offered under the ZEONOR™ (from Zeon Chemicals) and ARTON™ (from JSR Corporation) brands. A suitable method for making these copolymers by this ring-opening method is disclosed in U.S. Patent No. 5,191,026.

[0112] Arylcyclobutene oligomers useful as such curable adhesive materials are well known in the art. Suitable arylcyclobutene oligomers include, but are not limited to, those having the formula:

[0113] [ka] wherein B is an n-valent linking group; Ar is a polyvalent aryl group such that carbon atoms of the cyclobutene ring are bonded to adjacent carbon atoms on the same aromatic ring of Ar; m is an integer of 1 or greater; n is an integer of 1 or greater; and R 5 is a monovalent group. Preferably, the polyvalent aryl group Ar may be composed of 1 to 3 aromatic carbocyclic or heteroaromatic rings. Preferably, the aryl group comprises a single aromatic ring, more preferably a phenyl ring. The aryl group is optionally substituted with 1 to 3 groups selected from (C1-C6) alkyl, tri(C1-C6) alkylsilyl, (C1-C6) alkoxy and halo, preferably with one or more of (C1-C6) alkyl, tri(C1-C3) alkylsilyl, (C1-C3) alkoxy and chloro, more preferably with one or more of (C1-C3) alkyl, tri(C1-C3) alkylsilyl and (C1-C3) alkoxy. Preferably, the aryl group is unsubstituted. Preferably, n=1 or 2, more preferably n=1. Preferably, m=1 to 4, more preferably m=2 to 4, even more preferably m=2. Preferably, R 5 is selected from H and (C1-C6)alkyl, more preferably H and (C1-C3)alkyl. Preferably B contains one or more carbon-carbon double bonds (ethylenic unsaturation). Suitable monovalent B groups are preferably of the formula -[C(R 10 )=CR 11 ]xZ, where R 10 and R 11 is independently selected from hydrogen, (C1-C6) alkyl, and aryl; Z is hydrogen, (C1-C6) alkyl, aryl, siloxanyl, -COR 12 Each R 12is independently selected from H, (C1-C6)alkyl, aryl, aralkyl, and alkaryl; and x=1 or 2. Preferably, R 10 and R 11 is independently selected from H, (C1-C3) alkyl, and aryl, more preferably selected from H and (C1-C3) alkyl. 12 is preferably (C1-C3) alkyl, aryl and aralkyl. Z is preferably siloxyl. Preferred siloxyl groups are of the formula -[Si(R 13 )2-O]p-Si(R 13 )2-, where each R 13 is independently selected from H, (C1-C6) alkyl, aryl, aralkyl, and alkaryl; and p is an integer equal to or greater than 1. 13 is selected from (C1-C3) alkyl, aryl and aralkyl. Suitable aralkyl groups include benzyl, phenethyl and phenylpropyl.

[0114] Preferably, the arylcyclobutene oligomer comprises one or more oligomers of the following formula:

[0115] [ka] In the formula, each R 6 is independently selected from H and (C1-C6)alkyl, preferably selected from H and (C1-C3)alkyl; each R 7 is independently selected from (C1-C6)alkyl, tri(C1-C6)alkylsilyl, (C1-C6)alkoxy, and halo; each R 8 are independently a divalent ethylenically unsaturated organic group; 9 is independently selected from H, (C1-C6)alkyl, aralkyl, and phenyl; p is an integer equal to or greater than 1; and q is an integer from 0 to 3. 6 is preferably independently selected from H and (C-C) alkyl, more preferably each R 6is H. Each R7 is preferably independently selected from (C1-C6)alkyl, tri(C1-C3)alkylsilyl, (C1-C3)alkoxy and chloro, more preferably selected from (C1-C3)alkyl, tri(C1-C3)alkylsilyl and (C1-C3)alkoxy. Preferably each R 8 is independently selected from (C2-C6)alkenyl, more preferably each R 8 is -CH=CH-. Each R 9 is preferably selected from (C1-C3) alkyl, more preferably each R 9 is methyl. Preferably, p=1-5, more preferably p=1-3, and even more preferably p=1. Preferably, q=0. A particularly preferred arylcyclobutene oligomer, 1,3-bis(2-bicyclo[4.2.0]octa-1,3,5-trien-3-ylethenyl)-1,1,3,3-tetramethyldisiloxane ("DVS-bisBCB"), has the formula:

[0116] [ka]

[0117] The arylcyclobutene oligomers may be prepared by any suitable means, such as those described in U.S. Pat. Nos. 4,812,588; 5,136,069; 5,138,081 and International Publication WO 94 / 25903. Suitable arylcyclobutene oligomers are also commercially available under the CYCLOTENE brand available from Dow Electronic Materials. The arylcyclobutene oligomers may be used as is or may be further purified by any suitable means.

[0118] Vinyl aromatic oligomers that can be cured can be used as curable adhesive materials in the present invention. Such vinyl aromatic oligomers are usually oligomers of one or more reactive ethylenically unsaturated comonomers and vinyl aromatic monomers. Preferably, the vinyl aromatic monomer contains one vinyl group. Suitable vinyl aromatic monomers include unsubstituted vinyl aromatic monomers and substituted vinyl aromatic monomers in which one or more hydrogens are replaced with a substituent selected from the group consisting of (C1-C6) alkyl, (C1-C6) alkoxy, halo, and amino. Exemplary vinyl aromatic monomers include, but are not limited to, styrene, vinyl toluene, vinyl xylene, vinyl anisole, vinyl dimethoxy benzene, vinyl aniline, halostyrenes such as fluorostyrene, α-methyl styrene, β-methoxy styrene, ethyl vinyl benzene, vinyl pyridine, vinyl imidazole, vinyl pyrrole, and mixtures thereof. Preferred vinyl aromatic monomers are styrene, vinyl toluene, vinyl xylene, vinyl anisole, ethyl vinyl benzene, and mixtures thereof. Preferred reactive comonomers are those that contain reactive moieties, i.e., moieties capable of further polymerization (or crosslinking) after the formation of vinyl aromatic oligomer, such as allyl moieties or vinyl groups, in addition to the olefin (or ethylenically unsaturated) moieties used to form vinyl aromatic oligomer.Such reactive comonomers may suitably be any asymmetric diene or triene that can be further polymerized by Diels-Alder reaction after oligomerization with vinyl aromatic monomer.More preferably, reactive comonomers contain allyl moieties in addition to the ethylenically unsaturated moieties used to form vinyl aromatic oligomer, and even more preferably contain allyl ester moieties in addition to this ethylenically unsaturated moieties.Exemplary reactive comonomers useful for forming vinyl aromatic oligomers include, but are not limited to, vinylcyclohexene, vinyl ether, asymmetric dienes or trienes such as terpene monomers, dicyclopentadiene, diallyl maleate, allyl acrylate, allyl methacrylate, allyl cinnamate, diallyl fumarate, allyl tiglate, divinylbenzene, and mixtures thereof.Preferred reactive comonomers are diallyl maleate, allyl acrylate, allyl methacrylate, allyl cinnamate, diallyl fumarate, and mixtures thereof, more preferably diallyl maleate, allyl methacrylate, and mixtures thereof.Exemplary terpene monomers include, but are not limited to, limonene, dipentene, myrcene, and the like.It will be understood by those skilled in the art that one or more second comonomers may also be used to form vinyl aromatic oligomers.Such second comonomers are ethylenically unsaturated but do not contain reactive moieties. Exemplary second comonomers include, but are not limited to, (meth)acrylic acid, (meth)acrylamide, (C1-C10) alkyl (meth)acrylates, aromatic (meth)acrylates, substituted ethylene monomers, and poly(alkylene oxide) monomers.

[0119] The molar ratio of vinyl aromatic monomer:comonomer in such vinyl aromatic oligomer is preferably 99:1 to 1:99, more preferably 95:5 to 5:95, and even more preferably 90:10 to 10:90. Such vinyl aromatic oligomer may be prepared by any suitable method, for example, by any method known in the art. Usually, vinyl aromatic oligomer is prepared by free radical polymerization of vinyl aromatic monomer and comonomer. Preferred vinyl aromatic oligomer contains unreacted allyl moieties that can further cure such oligomer.

[0120] A wide variety of materials may be used as release additives in the temporary bonding composition, provided that such materials do not react with the adhesive material under storage and use conditions, and are non-curable under the conditions used to cure the adhesive material. In addition, the release additive should be compatible with the temporary bonding composition, i.e., the release additive must be dispersible, miscible, or otherwise substantially compatible with the adhesive material and any other components used in the temporary bonding composition, such as organic solvents. If an organic solvent (or mixed solvent system) is used in the temporary bonding composition, the release additive and the curable adhesive material must be soluble in such solvent. In the present invention, the release additives are sufficiently non-volatile so that they do not substantially evaporate under the conditions of use, i.e., they do not substantially evaporate during the deposition process, e.g., spin coating, or any subsequent heating step used to remove the organic solvent or to cure the adhesive material. When a film or layer of the temporary bonding composition is cast, e.g., by spin coating, much (or all) of the solvent evaporates. It is preferred that the release additive is soluble in any organic solvent used, but not completely soluble in the curable adhesive material. The release additive is predominantly hydrophilic relative to the cured adhesive material. Without being bound by theory, it is believed that upon curing of the adhesive material, the release additive phase separates and preferentially migrates toward the active surface of the wafer (a more hydrophilic surface compared to the carrier surface). The use of a suitable hydrophilic moiety in the release additive allows for complete dispersion, or preferably dissolution, of the release additive in the temporary bonding composition and allows for phase separation of the release additive during curing of the adhesive material with migration of the release additive toward the more hydrophilic surface. Any material that does not phase separate from the adhesive material during curing does not function as a release additive according to the present invention.

[0121] Generally, the release additive will contain one or more relatively hydrophilic moieties, such as one or more of oxygen, nitrogen, phosphorus, and sulfur-containing moieties. Suitable release additives include, but are not limited to: ethers, esters, carboxylates, alcohols, thioethers, thiols, amines, imines, amides, phosphate esters, sulfonate esters, and mixtures thereof. Preferably, the release additive contains one or more polar end groups, which contain one or more of oxygen, nitrogen, and sulfur, preferably oxygen. Exemplary polar end groups include alkoxy, aryloxy, hydroxy, carboxylate, alkoxycarbonyl, mercapto, alkylthio, primary amine, secondary amine, and tertiary amine, with preferred end groups being (C1-C6)alkoxy, (C6-C7)alkoxy, (C7-C8)alkoxy, (C9-C10)alkoxy, (C11-C12)alkoxy, (C12-C13)alkoxy, (C13-C14)alkoxy, (C14-C15)alkoxy, (C15-C16)alkoxy, (C16-C17)alkoxy, (C17-C18)alkoxy, (C18-C19)alkoxy, (C19-C20)alkoxy, (C19-C21)alkoxy, (C19-C22)alkoxy, (C19-C23)alkoxy, (C19-C24)alkoxy, (C19-C25)alkoxy, (C19-C26)alkoxy, (C19-C27)alkoxy, (C19-C28)alkoxy, (C19-C29)alkoxy, (C19-C21)alkoxy, (C19-C22)alkoxy, (C19-C23)alkoxy, (C19-C24)alkoxy, (C19-C25)alkoxy, 10 )aryloxy, hydroxy, carboxylate, (C1-C6)alkoxycarbonyl, mercapto, (C1-C6)alkylthio, amino, (C1-C6)alkylamino, and di(C1-C6)alkylamino, more preferably (C1-C6)alkoxy, (C6-C 10 )aryloxy, hydroxy, carboxylate, and (C1-C6)alkoxycarbonyl, and even more preferably (C1-C6)alkoxy, hydroxy, carboxylate, and (C1-C6)alkoxycarbonyl. Particularly preferred polar end groups are selected from hydroxy, methoxy, ethoxy, propoxy, butoxy, carboxyl, and acetoxy. Preferably, the release additive is silicone-free.

[0122] Suitable release additives have a number average molecular weight (Mn) of ≦10,000 Daltons, preferably ≦7500 Daltons, more preferably ≦7000 Daltons. The release additive has a minimum molecular weight (Mn) sufficient to render the release additive substantially non-volatile during use conditions (i.e., <5%, preferably <3%, more preferably ≦1% of the release additive volatilizes during use). Preferably the release additive has a Mn of ≧500 Daltons. A preferred range of Mn is 500-10,000 Daltons, more preferably 500-7500 Daltons, even more preferably 500-7000 Daltons. The release additive may be a linear polymer; a branched polymer, such as a dendritic polymer, a star polymer, or the like; a polymer particle, or the like; however, it is preferred that the release additive is a linear polymer or polymer particle, more preferably a linear polymer. Without being bound by theory, it is believed that linear polymers are better able to migrate through the cured adhesive material phase toward the hydrophilic wafer surface compared to branched polymers.

[0123] Polyethers are preferred release additives. Polyether compounds include alkylene oxide homopolymers and alkylene oxide copolymers, and these copolymers may be random or block. Polyalkylene oxide release additives may have a variety of polar end groups, preferably the polar end groups are hydroxy, (C1-C6)alkoxy, and (C1-C6)alkoxycarbonyl, more preferably hydroxy, (C1-C3)alkoxy, and acetoxy. Preferred polyether compounds are polyglycols (or polyalkylene oxides), such as poly(C1-C4)alkylene oxide compounds, which may contain a single type of alkylene oxide repeat unit, or two or more different types of alkylene oxide repeat units. Preferred polyether compounds include polyethylene glycols, polypropylene glycols, poly(1,3-propanediol), poly(tetrahydrofuran), ethylene oxide-propylene oxide copolymers, ethylene oxide-butylene oxide copolymers, and mixtures thereof. Preferably, when the release additive contains butylene oxide as a repeat unit, it is a copolymer with one or more different alkylene oxide repeat units. Those skilled in the art will understand that mixtures of release additives may be used in the temporary bonding composition of the present invention. Suitable release additives include polyethers sold under the product names PLURONIC®, TETRONIC and POLYTHF (available from BASF, Ludwigshafen, Germany), FORTEGRA (The Dow Chemical Company, Midland, Michigan), and TERATHANE (available from Invista, Wichita, Kansas), all of which may be used without further purification.

[0124] The second adhesive composition may contain, for example, the thermosetting polymer described below as a thermosetting adhesive component. As the thermosetting adhesive component, for example, the thermosetting polymer described in Japanese Patent No. 6,528,747 can be used. The thermosetting polymer is not particularly limited, but preferred examples include a siloxane bond-containing polymer (hereinafter also referred to as silicone A) having a weight average molecular weight of 3,000 to 500,000, which is composed of a repeating unit represented by the following formula (3) and, if necessary, a repeating unit represented by the following formula (4).

[0125] [Chemical formula] [In the formula, R 6 ~R 9 each independently represents a monovalent hydrocarbon group having 1 to 8 carbon atoms. Also, m represents an integer of 1 to 100. A and B are positive numbers satisfying 0 < A < 1, 0 < B < 1, and A + B = 1. T 1 and T 2 are divalent organic groups represented by the following formula (5).

[0126] [Chemical formula] (In the formula, A 1 is a single bond or a divalent organic group selected from the groups represented by the following formula

[0127] [Chemical formula] . R 10 and R 11 each independently represents an alkyl group or an alkoxy group having 1 to 4 carbon atoms. h is each independently 0, 1, or 2.)]

[0128] Examples of the monovalent hydrocarbon group represented by R 6 ~R 9 include alkyl groups such as methyl group and ethyl group, and aryl groups such as phenyl group. m is preferably an integer of 3 to 60, more preferably 8 to 40. Also, A is preferably 0.3 to 0.8, B is preferably 0.2 to 0.7, and it is preferable that A / B satisfies 0.1 to 20, and more preferably 0.5 to 5.

[0129] Further, as a preferable example of the thermosetting polymer, there is also a siloxane bond-containing polymer (hereinafter also referred to as silicone B) having a weight average molecular weight of 3,000 to 500,000, which is composed of a repeating unit represented by the following formula (6) and, if necessary, a repeating unit represented by the following formula (7).

[0130] [Chemical formula] [In the formula, R 12 ~R 15 each independently represents a monovalent hydrocarbon group having 1 to 8 carbon atoms. p represents an integer of 1 to 100. C and D are positive numbers satisfying 0 < C ≤ 1, 0 ≤ D < 1, and C + D = 1. T 3 and T 4 are divalent organic groups represented by the following formula (8).

[0131] [Chemical formula] (In the formula, A 2 is a single bond or a divalent organic group selected from the groups represented by the following formula

[0132] [Chemical formula] . R 16 and R 17 each independently is an alkyl group or an alkoxy group having 1 to 4 carbon atoms. k is each independently 0, 1, or 2.)]

[0133] In this case, examples of the monovalent hydrocarbon group represented by R 11 ~R 14 are the same as those exemplified as the one represented by R 5 ~R 8 . p is preferably an integer of 3 to 60, more preferably 8 to 40. Also, C is preferably 0.3 to 1, D is preferably 0 to 0.7, and C + D = 1.

[0134] The adhesive layer formed using the thermosetting polymer as the thermosetting adhesive component is preferably a layer of a cured product of a thermosetting resin composition mainly composed of silicone A or silicone B. Silicone A and silicone B can be used in combination. In this case, the ratio (polymerization ratio) is preferably silicone A:silicone B=0.1:99.9 to 99.9:0.1, more preferably silicone A:silicone B=20:80 to 80:20.

[0135] The thermosetting resin composition containing silicone A as a main component contains, for thermal curing, one or more crosslinking agents selected from an amino condensate modified with formalin or formalin-alcohol, a phenol compound having an average of two or more methylol groups or alkoxymethylol groups per molecule, and an epoxy compound having an average of two or more epoxy groups per molecule.

[0136] On the other hand, the thermosetting resin composition containing Silicone B as a main component contains, for thermal curing, one or more crosslinking agents selected from a phenol compound having an average of two or more phenol groups per molecule and an epoxy compound having an average of two or more epoxy groups per molecule.

[0137] Furthermore, the thermosetting resin composition containing silicone A and silicone B contains, for thermal curing, one or more crosslinking agents selected from epoxy compounds having, on average, two or more epoxy groups per molecule.

[0138] Examples of the amino condensate include melamine resins, urea resins, etc. Examples of melamine resins modified with formalin or formalin-alcohol include those obtained by subjecting modified melamine monomers (e.g., trimethoxymethyl monomethylol melamine) or their multimers (e.g., oligomers such as dimers and trimers) to addition condensation polymerization with formaldehyde according to a known method until a desired molecular weight is reached. These may be used alone or in combination of two or more.

[0139] Examples of urea resins modified with formalin or formalin-alcohol include methoxymethylated urea condensates, ethoxymethylated urea condensates, and propoxymethylated urea condensates. These can be used alone or in combination of two or more. Urea resins modified with formalin or formalin-alcohol can be prepared, for example, by modifying a urea condensate of a desired molecular weight with formalin by methylolating it according to a known method, or by further modifying it by alkoxylating it with an alcohol.

[0140] Examples of phenol compounds having two or more methylol groups or alkoxymethylol groups on average per molecule include (2-hydroxy-5-methyl)-1,3-benzenedimethanol and 2,2',6,6'-tetramethoxymethylbisphenol A. These may be used alone or in combination of two or more.

[0141] The epoxy compound having two or more epoxy groups on average in one molecule is not particularly limited, but examples thereof include bifunctional, trifunctional, tetrafunctional or higher polyfunctional epoxy resins, for example, EOCN-1020 (see the formula below), EOCN-102S, XD-1000, NC-2000-L, EPPN-201, GAN, and NC6000 manufactured by Nippon Kayaku Co., Ltd., and those represented by the formula below.

[0142] [ka]

[0143] Examples of phenol compounds having two or more phenol groups on average per molecule include m- or p-cresol novolak resins (e.g., EP-6030G manufactured by Asahi Organic Chemicals Co., Ltd.), trifunctional phenol compounds (e.g., Tris-P-PA manufactured by Honshu Chemical Industry Co., Ltd.), and tetrafunctional phenol compounds (e.g., TEP-TPA manufactured by Asahi Organic Chemicals Co., Ltd.).

[0144] The amount of the crosslinking agent in the thermosetting resin composition is preferably 0.1 to 50 parts by mass, more preferably 0.2 to 30 parts by mass, and further preferably 1 to 20 parts by mass, based on 100 parts by mass of the thermosetting polymer. The crosslinking agent may be used alone or in combination of two or more kinds.

[0145] The thermosetting resin composition may contain a curing catalyst such as an acid anhydride in an amount of 10 parts by mass or less based on 100 parts by mass of the thermosetting polymer.

[0146] <Method of manufacturing laminate> When the adhesive layer in the laminate is a single layer formed using the adhesive composition of the present invention, the method for producing the laminate of the present invention includes a step of forming the adhesive layer (an adhesive coating layer forming step and an adhesive layer forming step) and further includes other steps such as a lamination step, as necessary. The method for producing the laminate in this case will be described in detail in the section "First embodiment" below. In addition, when the adhesive layer in the laminate has two or more layers (multiple layers) of adhesive layers formed using the adhesive composition of the present invention, the manufacturing method of the laminate of the present invention includes a step of forming an adhesive layer (adhesive coating layer forming step and adhesive layer forming step), and further includes other steps such as a lamination step, as necessary. The manufacturing method of the laminate in this case will be described in detail in the section of <<Second embodiment>> below. However, in the second embodiment, the case where the adhesive layer has two layers will be described as an example. Furthermore, when the adhesive layer in the laminate includes a second adhesive layer in addition to the adhesive layer formed using the adhesive composition of the present invention, the manufacturing method of the laminate of the present invention includes a step of forming the adhesive layer (adhesive coating layer forming step and adhesive layer forming step) as well as a step of forming the second adhesive layer (second adhesive coating layer forming step and second adhesive layer forming step), and further includes other steps such as a lamination step, as necessary. The manufacturing method of the laminate in this case will be described in detail in the section <<Third embodiment>> below.

[0147] <<First embodiment>> The adhesive layer is formed through the adhesive coating layer forming step and the adhesive layer forming step.

[0148] <<<Adhesive Coating Layer Formation Process>>> In the adhesive coating layer forming step, an adhesive composition is applied to a semiconductor substrate having bumps to form an adhesive coating layer. The coating method is not particularly limited, but is usually a spin coating method. Alternatively, a method may be used in which a coating film is formed separately by a spin coating method or the like, and the sheet-like coating film is attached as an adhesive coating layer. The thickness of the adhesive coating layer is appropriately determined taking into consideration the desired thickness of the adhesive layer in the laminate, etc. When the adhesive composition contains a solvent, the composition may be preheated after application when forming an adhesive coating layer in order to remove the solvent. The preheating temperature is appropriately determined usually within the range of 90 to 130°C and 1 to 5 minutes, taking into consideration the boiling point of the solvent, the film thickness, the curing initiation temperature of the thermosetting adhesive component, and the thermal expansion temperature of the thermally expandable particles.

[0149] <<<Adhesive layer formation process>>> In the adhesive layer forming step, the adhesive coating layer is heated to cure the thermosetting adhesive component to form an adhesive layer. Heating can be carried out using a hot plate, an oven, or the like. In the present invention, the curing start temperature Tc (°C) of the thermosetting adhesive component is the curing start temperature exhibited by the thermosetting adhesive component used for this type of application, and is not particularly limited as long as it is not too high a temperature that may adversely affect the members and materials used together, but is usually 90 to 160°C, and preferably 100 to 150°C. The expansion start temperature Ts (°C) of the thermally expandable particles is determined appropriately taking into consideration the relationship with the curing start temperature of the thermosetting adhesive component, but is usually 70 to 160°C, and preferably 80 to 150°C. The heating temperature in the adhesive layer formation process is appropriately determined so as to achieve curing, taking into consideration the curing initiation temperature of the thermosetting adhesive component. From the viewpoint of achieving a sufficient curing rate of the thermosetting adhesive component, the heating temperature is usually 170°C or higher, preferably 200°C or higher, and the upper limit is usually 250°C. The heating time is preferably 1 to 20 minutes from the viewpoint of improving the throughput of the production of semiconductor substrates using the adhesive composition of the present invention.

[0150] The adhesive layer forming step is not particularly limited as long as it is a step in which the adhesive coating layer is heated in a state in which the support substrate and the adhesive coating layer are in contact with each other and the adhesive coating layer and the semiconductor substrate are in contact with each other to form an adhesive layer. For example, a semiconductor substrate having an adhesive coating layer formed thereon and a support substrate are arranged so that the two substrates (semiconductor substrate and support substrate) sandwich the adhesive coating layer, so that the support substrate and the adhesive coating layer are in contact with each other, and also so that the adhesive coating layer and the semiconductor substrate are in contact with each other, and then a heat treatment is performed. The heating temperature and time are not particularly limited as long as they are sufficient to cure the thermosetting adhesive component. The heating temperature is appropriately determined taking into consideration the curing initiation temperature of the thermosetting adhesive component and the heat resistance of the substrate used, but from the viewpoint of achieving a sufficient curing speed, it is preferably 120°C or higher, more preferably 170°C or higher, and even more preferably 200°C or higher, and from the viewpoint of preventing deterioration of each layer (including the support substrate and semiconductor substrate) constituting the laminate, it is preferably 250°C or lower. The heating time is appropriately determined depending on the heating temperature, but from the viewpoint of sufficiently promoting the curing of the thermosetting adhesive component, it is preferably 1 minute or more, and more preferably 5 minutes or more, and from the viewpoint of suppressing or avoiding adverse effects on each layer due to excessive heating, it is preferably 180 minutes or less, more preferably 120 minutes or less, even more preferably 60 minutes or less, and even more preferably 20 minutes or less. Heating can be carried out using a hot plate, an oven, or the like.

[0151] (Lamination process) Between the adhesive coating layer forming step and the adhesive layer forming step, a bonding step is preferably performed in order to ensure sufficient bonding between the semiconductor substrate and the support substrate. By performing bonding using the adhesive coating layer, which is a film with a certain degree of flexibility before becoming an adhesive layer, which is a cured film, better bonding can be realized with good reproducibility. The bonding step is not particularly limited as long as it allows bonding of the substrate and the layer and does not damage the substrate or the layer, but is typically a step in which a load is applied in the thickness direction of the support substrate and the semiconductor substrate, and more preferably a step in which a load is applied in the thickness direction of the support substrate and the semiconductor substrate under reduced pressure. The load is not particularly limited as long as it allows bonding of the substrate and the layer and does not damage the substrate or the layer, but is, for example, 10 to 1,000 N. The degree of reduced pressure is not particularly limited as long as it allows bonding of the substrate and the layer and does not damage the substrate or the layer, but is, for example, 10 to 10,000 Pa.

[0152] <<Second embodiment>> After a first adhesive layer is formed through an adhesive coating layer forming step and an adhesive layer forming step, a second adhesive layer is formed through steps similar to the adhesive coating layer forming step and the adhesive layer forming step. The first adhesive layer can be formed by applying an adhesive composition to a semiconductor substrate with bumps using a method similar to the adhesive coating layer formation process described above in the <<First embodiment>> to form an adhesive coating layer. Next, the adhesive coating layer is heated to cure the thermosetting adhesive component to form a first adhesive layer. The conditions for forming an adhesive layer from the adhesive coating layer are as described in the <<<Adhesive Layer Forming Step>>> section of the <<First embodiment>> above.

[0153] Next, the second adhesive layer is formed through an adhesive coating layer forming step and an adhesive layer forming step. The coating method used in the second adhesive coating layer formation step is not particularly limited, so long as the second adhesive composition is applied so as to contact either the supporting substrate or the first adhesive layer, and a method similar to the coating method described in the adhesive coating layer formation step of the above-mentioned <<First embodiment>> can be used. In the second adhesive layer forming step, the adhesive coating layer obtained in the second adhesive coating layer forming step is heated to cure the thermosetting adhesive component, thereby forming the second adhesive layer.

[0154] The second adhesive layer formation process is not particularly limited as long as it is a process in which the second adhesive coating layer is heated while the support substrate and the second adhesive coating layer are in contact with each other and the second adhesive coating layer and the first adhesive layer are in contact with each other, thereby forming the second adhesive layer. For example, using a semiconductor substrate having a first adhesive layer and a second adhesive coating layer formed thereon and a supporting substrate, or using a semiconductor substrate having a first adhesive layer formed thereon and a supporting substrate having a second adhesive coating layer formed thereon, two substrates (semiconductor substrate and supporting substrate) are arranged so as to sandwich the two layers (first adhesive layer and second adhesive coating layer) so that the supporting substrate and the second adhesive coating layer are in contact with each other and the second adhesive coating layer and the first adhesive layer are in contact with each other, and then a heat treatment is performed. The heating temperature and time are not particularly limited as long as they are sufficient to cure the thermosetting adhesive component. The heating conditions can be the same as those described in the adhesive layer forming step of the above-mentioned <<First embodiment>>, and the preferred conditions are also the same as those described above.

[0155] (Lamination process) Between the step of forming the second adhesive coating layer and the step of forming the second adhesive layer, a bonding step is preferably performed in order to ensure sufficient bonding between the semiconductor substrate and the support substrate. By performing bonding using the adhesive coating layer, which is a film with a certain degree of flexibility before it becomes an adhesive layer, which is a hardened film, better bonding can be achieved with good reproducibility. The lamination step can be carried out under the same conditions as those described in the above <<First embodiment>>, and the preferred conditions thereof are also the same as those described above.

[0156] <<Third embodiment>> After the adhesive layer is formed through the adhesive coating layer forming step and the adhesive layer forming step, a second adhesive layer is formed. The second adhesive layer is formed through a second adhesive coating layer forming step and a second adhesive layer forming step. The coating method used in the second adhesive coating layer formation step is not particularly limited, so long as the second adhesive composition containing a thermosetting adhesive component is coated so as to contact either the supporting substrate or the adhesive layer, and a method similar to the coating method described in the adhesive coating layer formation step section of the above <<First embodiment>> can be used, and the preferred conditions, etc. are also the same as those described above. In the second adhesive layer forming step, the second adhesive coating layer obtained in the second adhesive coating layer forming step is heated to cure the thermosetting adhesive component, thereby forming a second adhesive layer.

[0157] The second adhesive layer formation process is not particularly limited as long as it is a process in which the second adhesive coating layer is heated while the support substrate and the second adhesive coating layer are in contact with each other and the second adhesive coating layer and the adhesive layer are in contact with each other, thereby forming a second adhesive layer. For example, using a semiconductor substrate having an adhesive layer and a second adhesive coating layer formed thereon and a supporting substrate, or using a semiconductor substrate having an adhesive layer formed thereon and a supporting substrate having a second adhesive coating layer formed thereon, two substrates (semiconductor substrate and supporting substrate) are arranged so as to sandwich the two layers (adhesive layer and second adhesive coating layer) so that the supporting substrate and the second adhesive coating layer are in contact with each other and the second adhesive coating layer and the adhesive layer are in contact with each other, and then a heat treatment is performed. The heating temperature and time are not particularly limited as long as they are sufficient to cure the thermosetting adhesive component. The heating conditions can be the same as those described in the adhesive layer forming step of the above-mentioned <<First embodiment>>, and the preferred conditions are also the same as those described above.

[0158] (Lamination process) Between the second adhesive coating layer forming step and the second adhesive layer forming step, a bonding step is preferably performed in order to ensure sufficient bonding between the semiconductor substrate and the support substrate. By performing bonding using the adhesive coating layer, which is a film with a certain degree of flexibility before becoming an adhesive layer, which is a cured film, better bonding can be realized with good reproducibility. The lamination step can be carried out under the same conditions as those described in the above <<First embodiment>>, and the preferred conditions thereof are also the same as those described above.

[0159] (Method of manufacturing semiconductor substrate) The laminate of the present invention is used for temporary bonding for processing a semiconductor substrate, and is used in applications where the support substrate and the semiconductor substrate are separated after processing of the semiconductor substrate in the laminate. The method for manufacturing a semiconductor substrate of the present invention includes at least a processing step in which a semiconductor substrate is processed, and a peeling step in which the processed semiconductor substrate is separated from a supporting substrate, and further includes other steps such as a removing step as necessary.

[0160] <Processing process> The processing step is not particularly limited as long as it is a step in which the semiconductor substrate in the laminate according to the present invention is processed, and includes, for example, a polishing process, a through electrode formation process, and the like.

[0161] <<Polishing process>> The polishing process is not particularly limited as long as it is a process for polishing the surface of the semiconductor substrate opposite to the surface on which the bumps are present, thereby thinning the semiconductor substrate. For example, physical polishing using an abrasive or a grinding wheel may be used. The polishing process can be carried out using a general polishing device used for polishing semiconductor substrates. The polishing process reduces the thickness of the semiconductor substrate, and a semiconductor substrate thinned to a desired thickness is obtained. The thickness of the thinned semiconductor substrate is not particularly limited, but may be, for example, 10 to 300 μm, or 30 to 100 μm.

[0162] <<Through electrode formation process>> In some cases, a through electrode is formed in the polished semiconductor substrate to realize electrical continuity between the thinned semiconductor substrates when a plurality of thinned semiconductor substrates are stacked. Therefore, the method for manufacturing a semiconductor substrate may include a through electrode forming process for forming a through electrode in the polished semiconductor substrate after the polishing process and before the peeling process. The method for forming a through electrode in a semiconductor substrate is not particularly limited, but may be, for example, a method of forming a through hole and filling the formed through hole with a conductive material. The through holes are formed by, for example, photolithography. The through holes are filled with a conductive material by, for example, a plating technique.

[0163] <Peeling process> The peeling step is not particularly limited as long as it is a step in which the support substrate and the processed semiconductor substrate are separated after the processing step. For example, a method of mechanically peeling off using a machine having a sharp part (so-called debonder) can be mentioned. Specifically, for example, a sharp part is inserted between the semiconductor substrate and the support substrate, and then the semiconductor substrate and the support substrate are separated. Since the first adhesive layer of the laminate of the present invention has voids, the first adhesive layer is usually broken appropriately, and the processed semiconductor substrate can be appropriately separated from the support substrate.

[0164] <Other processes> <<Removal process>> In the removal step, the adhesive layer residue attached to the processed semiconductor substrate is removed after the peeling step. The removal method is not particularly limited, but examples include dissolving and removing with a cleaner containing salt. Removal may also be performed using a removal tape or the like. At this time, care must be taken not to damage the bumps.

[0165] An example of an embodiment in which the production of a laminate and the production of a thinned wafer are carried out in a series will be described with reference to Figs. 2A to 2F. Another example of an embodiment in which the production of a laminate and the production of a thinned wafer are carried out in a series will be described with reference to Figs. 3A to 3H. 2A to 2F are diagrams for explaining one embodiment for producing a laminate and a thinned wafer. First, a wafer 1 having bumps 1a is prepared (FIG. 2A). Next, an adhesive composition is applied by spin coating using a coating device 10 onto the surface of the wafer 1 on which the bumps 1a are present, to form an adhesive coating layer 2a (FIG. 2B). Next, a support substrate 4 is placed on the adhesive coating layer 2a (FIG. 2C). Next, the wafer 1 and the supporting substrate 4 are bonded together under reduced pressure so as to sandwich the adhesive coating layer, and then a heating device (hot plate) 11 is placed on the side of the wafer 1 opposite to the side on which the bumps 1a are present, and the adhesive coating layer 2a is heated by the heating device 11 to harden the thermosetting adhesive component and convert it into an adhesive layer 2 (Figure 2D). A laminate is obtained by the steps shown in FIGS. 2A to 2D. Next, an example of manufacturing a thinned wafer will be described. Next, a polishing device (not shown) is used to polish the surface of the wafer 1 opposite to the surface on which the bumps 1a are present, thereby thinning the wafer 1 (FIG. 2E). Note that the thinned wafer 1 may be subjected to the formation of through electrodes, etc. Next, a peeling device (not shown) is used to peel off the thinned wafer 1 from the support substrate 4 (FIG. 2F). Peeling off the adhesive layer 2 peels off the thinned wafer 1 from the support substrate 4. When the adhesive layer is peeled off, it does not matter if a remainder of the adhesive layer remains on the wafer 1 where the bumps 1a are present. In this case, the remainder of the adhesive layer can be removed, for example, by the method described in the above-mentioned <Removal step>. In this manner, a thinned wafer 1 is obtained.

[0166] 3A to 3H are diagrams for explaining another embodiment for producing a laminate and a thinned wafer. First, a wafer 1 having bumps 1a is prepared (FIG. 3A). Next, an adhesive composition is applied by spin coating using a coating device 12 onto the surface of the wafer 1 on which the bumps 1a are present, to form an adhesive coating layer 2a (FIG. 3B). Next, a heating device (hot plate) 13 is placed on the side of the wafer 1 opposite to the side on which the bumps 1a are present, and the adhesive coating layer 2a is heated by the heating device 13, thereby hardening the thermosetting adhesive component and converting it into an adhesive layer 2 (Figure 3C). Next, a second adhesive composition is applied onto the adhesive layer 2 by spin coating using an application device 14 to form a second adhesive coating layer 3a (FIG. 3D). Next, a support substrate 4 is placed on the second adhesive coating layer 3a (FIG. 3E). Next, the wafer 1 and the supporting substrate 4 are bonded together under reduced pressure so as to sandwich the adhesive layer and the second adhesive coating layer, and then a heating device (hot plate) 15 is placed on the side of the wafer 1 opposite to the side on which the bumps 1a are present, and the adhesive coating layer 3a is heated by the heating device 15 to harden the thermosetting adhesive component and convert it into an adhesive layer 3 (Figure 3F). A laminate is obtained by the steps shown in FIGS. 3A to 3F. Next, an example of manufacturing a thinned wafer will be described. Next, a polishing device (not shown) is used to polish the surface of the wafer 1 opposite to the surface on which the bumps 1a are present, thereby thinning the wafer 1 (FIG. 3G). Note that the thinned wafer 1 may be subjected to the formation of through electrodes, etc. Next, a peeling device (not shown) is used to peel off the thinned wafer 1 from the support substrate 4 (FIG. 3H). Peeling off the adhesive layer 2 peels off the thinned wafer 1 from the support substrate 4. When the adhesive layer is peeled off, it does not matter if a remainder of the adhesive layer remains on the wafer 1 where the bumps 1a are present. In this case, the remainder of the adhesive layer can be removed, for example, by the method described in the above-mentioned <Removal step>. In this manner, a thinned wafer 1 is obtained.

[0167] The method for improving the storage stability of an adhesive composition of the present invention is a method for improving the storage stability of an adhesive composition used to form an adhesive layer for temporary bonding to process a semiconductor substrate, which contains a thermosetting adhesive component containing polyorganosiloxane and thermally expandable particles, and the content of the thermally expandable particles is 3.5 mass% or less relative to the thermosetting adhesive component. The preferred conditions for the thermosetting adhesive component, the thermally expandable particles, and their content are the same as those described above. According to the method of the present invention for improving the storage stability of an adhesive composition, when the adhesive composition is stored at 23°C, excellent storage stability can be achieved in which no precipitation is observed in the composition when observed with the naked eye, usually even after a storage period of at least 5 days, in a preferred embodiment at least 10 days, in a more preferred embodiment at least 20 days, in an even more preferred embodiment at least 30 days, and in an even more preferred embodiment at least 60 days. EXAMPLES

[0168] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. The following apparatuses were used.

[0169] [Device] (1) Mixer: Thinky Corporation, Planetary Planetary Mixer ARE-500 (2) Vacuum bonding equipment: SUSS MicroTec, manual bonder (3) DSC: TA Instruments Co., Ltd. Differential Scanning Calorimeter Q-2000 (4) Peeling device: Manual debonder, manufactured by SUSS MicroTec Co., Ltd.

[0170] The physical properties of the thermally expandable particles used (all manufactured by Matsumoto Yushi Seiyaku Co., Ltd.) are shown in Table 1. The thermally expandable particles used all had a thermoplastic resin forming a shell that was an acrylonitrile copolymer shell, and the volatile substance therein was a hydrocarbon.

[0171] [Table 1]

[0172] [1] Preparation of thermosetting adhesive component (hereinafter also referred to as adhesive component) [Preparation Example 1] In a 600 mL stirring vessel dedicated to the planetary centrifugal mixer, 80 g of an MQ resin (manufactured by Wacker Chemical Industries, Ltd.) containing a polysiloxane skeleton and a vinyl group as the component (a1), 2.52 g of an SiH group-containing linear polydimethylsiloxane (manufactured by Wacker Chemical Industries, Ltd.) having a viscosity of 100 mPa s as the component (a2), 5.89 g of an SiH group-containing linear polydimethylsiloxane (manufactured by Wacker Chemical Industries, Ltd.) having a viscosity of 70 mPa s as the component (a2), and 0.22 g of 1-ethynyl-1-cyclohexanol (manufactured by Wacker Chemical Industries, Ltd.) as the component (A3) were placed and stirred for 5 minutes with a stirrer. To the resulting mixture, 0.147 g of a platinum catalyst (manufactured by Wacker Chemical Co.) as the component (A2) and 5.81 g of a vinyl group-containing linear polydimethylsiloxane (manufactured by Wacker Chemical Co.) having a viscosity of 1,000 mPa s as the component (a1) were stirred for 5 minutes with a stirrer, and 3.96 g of the mixture obtained separately was added, and the mixture was stirred for 5 minutes with a stirrer. Finally, the resulting mixture was filtered through a 300 mesh nylon filter to obtain an adhesive component.

[0173] [2] Preparation of adhesive composition

[0174] [Example 1-1] In a 600 mL stirring vessel for a planetary centrifugal mixer, 30 g of the adhesive component obtained in Preparation Example 1, 0.15 g of thermally expandable particles FN-80GSD, and 0.6 g of propylene glycol-1-monomethyl ether-2-acetate (manufactured by Tokyo Chemical Industry Co., Ltd., the same applies below) were placed and stirred for 5 minutes with a stirrer. Finally, the resulting mixture was filtered through a 300 mesh nylon filter to obtain an adhesive composition.

[0175] [Example 1-2] In a 600 mL stirring vessel for a planetary centrifugal mixer, 30 g of the adhesive component obtained in Preparation Example 1, 0.30 g of thermally expandable particles FN-80GSD, and 0.6 g of propylene glycol-1-monomethyl ether-2-acetate were placed and stirred for 5 minutes with a stirrer. Finally, the mixture obtained was filtered through a 300 mesh nylon filter to obtain an adhesive composition.

[0176] [Examples 1-3] In a 600 mL stirring vessel for a planetary centrifugal mixer, 30 g of the adhesive component obtained in Preparation Example 1, 0.60 g of thermally expandable particles FN-80GSD, and 0.6 g of propylene glycol-1-monomethyl ether-2-acetate were placed and stirred for 5 minutes with a stirrer. Finally, the resulting mixture was filtered through a 300 mesh nylon filter to obtain an adhesive composition.

[0177] [Examples 1-4] In a 600 mL stirring vessel for a planetary centrifugal mixer, 30 g of the adhesive component obtained in Preparation Example 1, 0.90 g of thermally expandable particles FN-80GSD, and 0.6 g of propylene glycol-1-monomethyl ether-2-acetate were placed and stirred for 5 minutes with a stirrer. Finally, the resulting mixture was filtered through a 300 mesh nylon filter to obtain an adhesive composition.

[0178] [Comparative Example 1-1] In a 600 mL stirring vessel for a planetary centrifugal mixer, 30 g of the adhesive component obtained in Preparation Example 1, 1.2 g of thermally expandable particles FN-80GSD, and 0.6 g of propylene glycol-1-monomethyl ether-2-acetate were placed and stirred for 5 minutes with a stirrer. Finally, the mixture obtained was filtered through a 300 mesh nylon filter to obtain an adhesive composition.

[0179] [Comparative Example 1-2] In a 600 mL stirring vessel for a planetary centrifugal mixer, 30 g of the adhesive component obtained in Preparation Example 1, 1.5 g of thermally expandable particles FN-80GSD, and 0.6 g of propylene glycol-1-monomethyl ether-2-acetate were placed and stirred for 5 minutes with a stirrer. Finally, the resulting mixture was filtered through a 300 mesh nylon filter to obtain an adhesive composition.

[0180] [Comparative Preparation Example 1] In a 600 mL stirring vessel for the planetary centrifugal mixer, 30 g of synthetic rubber adhesive Threebond 1521B (Threebond Fine Chemical Co., Ltd.), 0.15 g of thermally expandable particles FN-80GSD, and 0.6 g of propylene glycol-1-monomethyl ether-2-acetate were placed and stirred for 5 minutes with a stirrer. Finally, the resulting mixture was filtered through a 300 mesh nylon filter to obtain an adhesive composition.

[0181] [3] Preparation of sample substrate [Production Example 1] A substrate (wafer) with bumps was cut to prepare a 4cm x 4cm sample substrate as the device wafer (semiconductor substrate). The number of bumps per sample substrate was 5044, and the bump structure consisted of copper pillars, tin-silver (1.8wt% silver) caps, and nickel between the pillars and caps.

[0182] [Production Example 2] A silicon wafer was cut to prepare a sample substrate of 4 cm x 4 cm for use as the device wafer (semiconductor substrate).

[0183] [4] Preparation of laminate for evaluation [Comparative Example 2-1] The adhesive component obtained in Preparation Example 1 was spin-coated onto the bump-bearing surface of the sample substrate obtained in Manufacturing Example 1 so that the film thickness in the final laminate was approximately 60 μm, forming an adhesive coating layer. Then, using a bonding device, the sample substrate (silicon wafer) and a 100 mm glass wafer as a support substrate were bonded together so as to sandwich the adhesive coating layer, and then the sample substrate was placed face down and heated on a hot plate at 200°C for 10 minutes to produce a laminate. The bonding was performed at a temperature of 23°C and a reduced pressure of 1,500 Pa.

[0184] [Comparative Example 2-2] The adhesive component obtained in Preparation Example 1 was spin-coated onto the bump-bearing surface of the sample substrate obtained in Manufacturing Example 1 so that the film thickness in the final laminate was approximately 10 μm, and then the resulting laminate was heated on a hot plate at 200° C. for 5 minutes to form an adhesive layer. Furthermore, the adhesive component obtained in Preparation Example 1 was spin-coated onto the adhesive layer of the sample substrate so that the film thickness in the final laminate was approximately 50 μm, forming a second adhesive coating layer on the adhesive layer. Then, using a bonding device, the sample substrate (silicon wafer) and the glass wafer were bonded together so as to sandwich the adhesive layer and the second adhesive coating layer, and then the sample substrate was placed face down and heated on a hot plate at 200°C for 10 minutes to produce a laminate. The bonding was performed at a temperature of 23°C and a reduced pressure of 1,500 Pa.

[0185] [Example 2-1] The adhesive composition obtained in Example 1-1 was spin-coated onto the bump-bearing surface of the sample substrate obtained in Production Example 1 so that the film thickness in the final laminate was approximately 60 μm, forming an adhesive coating layer on the sample substrate. Then, using a bonding device, the sample substrate (silicon wafer) and a 100 mm glass wafer as a support substrate were bonded together so as to sandwich the adhesive coating layer, and then the sample substrate was placed face down and heated on a hot plate at 200°C for 10 minutes to produce a laminate. The bonding was performed at a temperature of 23°C and a reduced pressure of 1,500 Pa.

[0186] [Example 2-2] The adhesive composition obtained in Example 1-1 was spin-coated onto the bump-bearing surface of the sample substrate obtained in Production Example 1 so that the film thickness in the final laminate was approximately 30 μm, and then the substrate was heated on a hot plate at 200° C. for 5 minutes to form an adhesive layer on the sample substrate. Furthermore, the adhesive component obtained in Preparation Example 1 was spin-coated onto the adhesive layer of the sample substrate so that the film thickness in the final laminate was approximately 30 μm, forming a second adhesive coating layer on the adhesive layer. Then, using a bonding device, the sample substrate (silicon wafer) and a 100 mm glass wafer as a support substrate were bonded together so as to sandwich the adhesive layer and the second adhesive coating layer, and then the sample substrate was placed face down and heated on a hot plate at 200°C for 10 minutes to produce a laminate. The bonding was performed at a temperature of 23°C and a reduced pressure of 1,500 Pa.

[0187] [Example 2-3] The adhesive composition obtained in Example 1-1 was spin-coated onto the bump-bearing surface of the sample substrate obtained in Production Example 1 so that the film thickness in the final laminate was approximately 10 μm, and then the substrate was heated on a hot plate at 200° C. for 5 minutes to form an adhesive layer on the sample substrate. Furthermore, the adhesive component obtained in Preparation Example 1 was spin-coated onto the adhesive layer of the sample substrate so that the film thickness in the final laminate was approximately 50 μm, forming a second adhesive coating layer on the adhesive layer. Then, using a bonding device, the sample substrate (silicon wafer) and a 100 mm glass wafer as a support substrate were bonded together so as to sandwich the adhesive layer and the second adhesive coating layer, and then the sample substrate was placed face down and heated on a hot plate at 200°C for 10 minutes to produce a laminate. The bonding was performed at a temperature of 23°C and a reduced pressure of 1,500 Pa.

[0188] [Example 2-4] The adhesive composition obtained in Example 1-2 was spin-coated onto the bump-bearing surface of the sample substrate obtained in Production Example 1 so that the film thickness in the final laminate was approximately 60 μm, forming an adhesive coating layer on the sample substrate. Then, using a bonding device, the sample substrate (silicon wafer) and a 100 mm glass wafer as a support substrate were bonded together so as to sandwich the adhesive coating layer, and then the sample substrate was placed face down and heated on a hot plate at 200°C for 10 minutes to produce a laminate. The bonding was performed at a temperature of 23°C and a reduced pressure of 1,500 Pa.

[0189] [Example 2-5] The adhesive composition obtained in Example 1-2 was spin-coated onto the bump-bearing surface of the sample substrate obtained in Production Example 1 so that the film thickness in the final laminate was approximately 30 μm, and then the substrate was heated on a hot plate at 200° C. for 5 minutes to form an adhesive layer on the sample substrate. Furthermore, the adhesive component obtained in Preparation Example 1 was spin-coated onto the adhesive layer of the sample substrate so that the film thickness in the final laminate was approximately 30 μm, forming a second adhesive coating layer on the adhesive layer. Then, using a bonding device, the sample substrate (silicon wafer) and a 100 mm glass wafer as a support substrate were bonded together so as to sandwich the adhesive layer and the second adhesive coating layer, and then the sample substrate was placed face down and heated on a hot plate at 200°C for 10 minutes to produce a laminate. The bonding was performed at a temperature of 23°C and a reduced pressure of 1,500 Pa.

[0190] [Example 2-6] The adhesive composition obtained in Example 1-2 was spin-coated onto the bump-bearing surface of the sample substrate obtained in Production Example 1 so that the film thickness in the final laminate was approximately 10 μm, and then the substrate was heated on a hot plate at 200° C. for 5 minutes to form an adhesive layer on the sample substrate. Furthermore, the adhesive component obtained in Preparation Example 1 was spin-coated onto the adhesive layer of the sample substrate so that the film thickness in the final laminate was approximately 50 μm, forming a second adhesive coating layer on the adhesive layer. Then, using a bonding device, the sample substrate (silicon wafer) and a 100 mm glass wafer as a support substrate were bonded together so as to sandwich the adhesive layer and the second adhesive coating layer, and then the sample substrate was placed face down and heated on a hot plate at 200°C for 10 minutes to produce a laminate. The bonding was performed at a temperature of 23°C and a reduced pressure of 1,500 Pa.

[0191] [5] Peel test of laminate Using a hot plate, the laminates obtained in Comparative Examples 2-1 to 2-2 and Examples 2-1 to 2-6 were subjected to high-temperature treatment. The treatment was performed according to the following procedure. The laminate was placed with the support substrate facing down on a hot plate set at 300°C and heated for 5 minutes. After cooling, a wedge-shaped member was inserted between the semiconductor substrate and the support substrate using a peeling device to confirm whether the semiconductor substrate (substrate with bumps) could be peeled off from the laminate. The results are shown in Table 2.

[0192] [Table 2]

[0193] As shown in Table 2, the substrate could not be peeled off from the laminates having an adhesive layer obtained only from adhesive components that did not contain thermally expandable particles (Comparative Examples 2-1 and 2-2), whereas the substrate could be peeled off from the laminates having an adhesive layer obtained from an adhesive composition that contained thermally expandable particles (Examples 2-1 to 2-6).

[0194] [6] Storage test of adhesive composition The adhesive compositions obtained in Examples 1-1 to 1-4 and Comparative Examples 1-1 to 1-2 were each stored in a glass screw tube at 23°C for 5 days, and the presence or absence of precipitation after storage was visually confirmed. The results are shown in Table 3. Note that no precipitation was observed in any of the adhesive compositions immediately after preparation.

[0195] [Table 3]

[0196] As shown in Table 3, precipitation was observed in adhesive compositions in which the amount of thermally expandable particles relative to the adhesive components exceeded 3.5 mass%, whereas no precipitation was observed in adhesive compositions in which the amount of thermally expandable particles relative to the adhesive components was 3.5 mass% or less.

[0197] [7] Observation of the adhesive layer (film after heating) [Reference Examples 1-2 and Comparative Reference Examples 1-2] The adhesive compositions obtained in Examples 1-1 and 1-2, the adhesive components obtained in Preparation Example 1, and the adhesive composition obtained in Comparative Preparation Example 1 were each spin-coated onto the sample substrate obtained in Production Example 2 so that the final film thickness was about 10 μm, and then the sample substrate was placed down and heated on a hot plate at 200 ° C for 5 minutes to form an adhesive layer on the sample substrate. The adhesive layer on the sample substrate was then observed with an optical microscope. At this time, the adhesive layer was evaluated as "good" when it was confirmed that the porous state was in about 30% or more of the area in the field of view observed with the optical microscope, as "not good" when it was confirmed that the porous state was in about less than 30%, and as "bad" when the porous state was not confirmed at all. The results are shown in Table 4. In Table 4, the results using the adhesive compositions obtained in Examples 1-1 and 1-2 correspond to Reference Examples 1 and 2, the results using the adhesive components obtained in Preparation Example 1 correspond to Comparative Reference Example 1, and the results using the adhesive composition obtained in Comparative Preparation Example 1 correspond to Comparative Reference Example 2.

[0198] [Table 4]

[0199] As shown in Table 4, the adhesive layer obtained from the adhesive composition containing thermally expandable particles (Reference Examples 1-2) of the laminate that could be peeled off well was confirmed to have a porous state over an area of ​​about 30% or more, whereas the adhesive layer obtained from the adhesive component not containing thermally expandable particles (Comparative Reference Example 1) of the laminate that could not be peeled off was confirmed to have a porous state over an area of ​​about less than 30%. Moreover, when a synthetic rubber adhesive component was used instead of the curable adhesive component (Comparative Reference Example 2), no porous state was confirmed at all. Since the adhesive composition of the present invention contains thermoexpandable particles as well as a thermosetting adhesive component, during the process of heating the adhesive composition and curing the thermosetting adhesive component to produce an adhesive layer, gas is generated from the thermoexpandable particles, which results in the adhesive layer curing in a state in which voids (porosity) are generated in the adhesive layer.It is presumed that these voids cause a decrease in the adhesive ability of the adhesive layer compared to a case in which there are no voids, resulting in good releasability.

[0200] [8] Confirm the hardening start temperature Tc (℃) of the thermosetting adhesive component [Reference example 3] 5 mg of the adhesive component obtained in Preparation Example 1 was weighed out and placed in an aluminum pan, and the calorific value was measured using a DSC. The temperature was increased from room temperature (23°C) to 300°C at a rate of 10°C / min. The calorific value is plotted on the vertical axis and the temperature on the horizontal axis, and the temperature at which the peak of the calorific value was confirmed was taken as the curing initiation temperature of the adhesive component obtained in Preparation Example 1. As a result of the measurement, the curing initiation temperature Tc (°C) of the adhesive component obtained in Preparation Example 1 was 125°C. [Industrial Applicability]

[0201] According to the present invention, the number of layers interposed between the semiconductor substrate and the support substrate can be reduced, and when the semiconductor substrate and the support substrate are separated after processing of the semiconductor substrate, the semiconductor substrate can be easily peeled off from the adhesive layer, and a laminate in which the quality stability of the adhesive layer is guaranteed can be obtained, which is useful for producing processed semiconductor substrates. [Explanation of symbols]

[0202] 1 wafer 1a Bump 2 Adhesive layer 2a Adhesive coating layer 3 Second adhesive layer 3a Second adhesive coating layer 4 Support substrate 10 Coating equipment 11 Heating device 12 Coating equipment 13 Heating device 14 Coating equipment 15 Heating device

Claims

1. An adhesive composition used to form an adhesive layer for temporary bonding in order to process a semiconductor substrate, A thermosetting adhesive component and a thermally expandable particle are included, The thermosetting adhesive component contains a polyorganosiloxane, The adhesive composition contains the thermally expandable particles in an amount of 3.5 mass% or less based on the thermosetting adhesive component.

2. The adhesive composition according to claim 1 , wherein the thermosetting adhesive component is a component that cures by a hydrosilylation reaction.

3. A laminate including an adhesive layer interposed between a semiconductor substrate and a support substrate and in contact with the semiconductor substrate, A laminate, wherein the adhesive layer is a layer formed from the adhesive composition according to claim 1 or 2.

4. A method for improving the storage stability of an adhesive composition used to form an adhesive layer for temporary bonding for processing a semiconductor substrate, the adhesive composition comprising a thermosetting adhesive component containing polyorganosiloxane and thermally expandable particles, comprising: A method for improving the storage stability of an adhesive composition, comprising: setting the content of the thermally expandable particles to 3.5 mass % or less relative to the thermosetting adhesive component.

Citation Information

Patent Citations

  • Heat-resistant pressure-sensitive adhesive tape for production of semiconductor device and method for producing semiconductor device using the tape

    EP2639277A1

  • Active energy ray-curable resin composition with thermal peelability

    JP2007326917A

  • Semiconductor circuit forming film and method of manufacturing semiconductor circuit employing the same

    JP2008140852A

  • Adhesive composition for temporary fixation and working method of parts

    JP2011074245A

  • Pressure sensitive adhesive sheet

    JP2015168711A